Low water content composition

By using a low-water content composition combining a saturated fatty acid sodium carboxylate crystal agent with a mesh microstructure and a polyethylene glycol (PEG) domain, the shortcomings of existing solid soluble compositions in terms of temperature and moisture resistance are solved, and efficient solubility and stability improvement are achieved.

CN119585410APending Publication Date: 2025-03-07PROCTER & GAMBLE CO
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202380052630.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-12
Filing Date
2023-08-08
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing solid soluble compositions have shortcomings in their mild and moisture resistance and are difficult to dissolve effectively in water, limiting their use in various applications.

Method used

Using saturated fatty acid sodium carboxylate with 8 to 12 carbon atoms as crystallizer, a solid soluble composition (SDC) domain with a reticular microstructure is formed by processing and combining with the polyethylene glycol (PEG) domain to form a low moisture content composition.

Benefits of technology

The composition is efficiently dissolved in water, temperature and humidity resistance, and improves its stability and effect in detergents, drugs and other applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119585410A_ABST
    Figure CN119585410A_ABST
Patent Text Reader

Abstract

A low moisture content composition includes a solid soluble composition domain having a crystallizing agent and a PEGC domain.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The low water content composition comprises a solid soluble composition (SDC) domain having a network microstructure formed by a dry sodium fatty acid carboxylate preparation, and a polyethylene glycol domain (PEGC). Background Art

[0002] There are considerable challenges in formulating effective solid soluble compositions. The composition needs to be physically stable, preferably resistant to temperature and moisture, but still be able to perform the desired function by dissolving in solution and leaving little or no material behind. Solid soluble compositions are well known in the art and have been used in several applications such as detergents, oral and body medications, disinfectants, and cleaning compositions.

[0003] Surprisingly, a solid soluble composition (SDC) having a network microstructure formed from dried sodium fatty acid carboxylates can be produced that can contain high levels of actives that are easily solubilized in water and are also both temperature and humidity resistant, allowing for supply chain stability. It was discovered that low water content compositions having both domains of PEGC and SDC offer significant advantages over current solid compositions such as beads, including enhanced solubilization rates, sustainability, moisture control, increased sourcing opportunities, cost reduction, lightweighting for efficient e-commerce shipping, and protection of incompatible chemical ingredients. Summary of the invention

[0004] A low water content composition is provided, comprising: at least one solid soluble composition domain (SDC) having a crystallizing agent; at least one polyethylene glycol domain (PEGC); an active agent; and wherein the crystallizing agent is a sodium salt of a saturated fatty acid having 8 to about 12 carbon atoms; wherein the active agent is present in at least one of the SDC or the PEGC.

[0005] A low moisture content composition is provided which substantially dissolves during normal use and is composed of: a solid soluble composition (SDC) domain made from a crystallizing agent; a polyethylene glycol (PEGC) domain; and water; wherein the crystallizing agent is a sodium fatty acid carboxylate having 8 to about 12 carbon atoms; wherein the amount of water is less than 10% by weight of the final low moisture content composition as determined by the "Moisture Test Method".

[0006] Provided is a method for producing a low water content composition, comprising: mixing - heating a crystallizing agent and an aqueous phase until the crystallizing agent is substantially dissolved, cooling to a temperature before the crystallizing agent significantly crystallizes in the form of a SDCM; forming - forming the SDC into a designed shape and size by cooling the solid soluble composition mixture to below the crystallization temperature and allowing the solid soluble composition mixture to crystallize into an intermediate rheological solid; drying - removing excess water and producing a solid soluble composition (SDC) by removing between about 90% and about 99% of the water (as determined by the "Water Test Method") from the intermediate rheological solid composition to produce a solid soluble composition having an average solubility percentage greater than 5% at 37°C (as determined by the "Dissolution Test Method"); providing polyethylene glycol (PEGC); mixing SDC and PEGC to produce a low water content composition having an SDC domain and a PEGC domain; wherein an active agent is added to at least one of the SDC domain or the PEGC domain. BRIEF DESCRIPTION OF THE DRAWINGS

[0007] Although the specification ends with claims that specifically point out and clearly claim the subject matter of the present disclosure, it is believed that the present disclosure can be more fully understood from the following description in conjunction with the accompanying drawings. Some of these figures may have been simplified by omitting selected elements in order to more clearly show other elements. Such omissions of elements in certain figures do not necessarily indicate the presence or absence of a particular element in any exemplary embodiment unless such is clearly described in the corresponding text description. The drawings are not drawn to scale.

[0008] Figure 1A A scanning electron micrograph (SEM) of crystallization agent crystals is shown.

[0009] Figure 1B Scanning electron micrograph (SEM) showing a network microstructure made of crystallized crystallization agent in an SDC domain.

[0010] Figure 2A Scanning electron micrograph (SEM) showing active flavor capsules (eg, red arrows, top) dispersed in the network microstructure of SDC domains.

[0011] Figure 2B Scanning electron micrograph (SEM) showing flavor capsules dispersed in the network microstructure of SDC domains.

[0012] Figure 3 is a graph showing the amount of perfume in the headspace above dry rubbed fabrics treated with a viable amount of commercial product (about 1 gram perfume capsule, capped top) versus the composition of the present invention (about 2.5 grams perfume capsule, 1 / 2 capped). The composition of the present invention has much more perfume in the air and much less product added to the wash liquor.

[0013] Figure 4A , Figure 4B and Figure 4C Shown is the dissolution behavior of SDC prepared with different combinations of crystallization agents relative to commercial PEG, as determined using the "Dissolution Test Method".

[0014] Figure 5 is a graph showing the stabilization temperatures of the SDC domains of three compositions of the present invention measured using the "Thermal Stability Test Method".

[0015] Figure 6 is a graph showing the hydration stability of inventive composition SDC domains and comparative composition SDC domains when exposed to different relative humidities as measured by moisture absorption at 25°C using the "Humidity Test Method".

[0016] Figure 7 is a graphic representation of particles in a low water content composition as described in Example 1.

[0017] Figure 8 is a graphic representation of particles in a low water content composition as described in Example 2.

[0018] Fig. 9 is a graphic representation of particles in a low water content composition as described in Example 3.

[0019] Fig.10 is a graphic representation of particles in a low water content composition as described in Example 4.

[0020] Fig.11A A representative scanning electron micrograph (SEM) of a comparative composition prepared from potassium palmitate (KC16) is shown, showing plate-like crystals.

[0021] Fig. 11B A representative scanning electron micrograph (SEM) of a comparative composition prepared from triethanolamine palmitate (TEA C16) is shown, showing plate-like crystals. DETAILED DESCRIPTION

[0022] The present invention includes low water content compositions that are substantially completely soluble in aqueous environments. The low water content compositions comprise at least one solid soluble composition (SDC) domain having a crystalline network, and at least one polyethylene glycol composition (PEGC) domain. The crystalline network ("network") comprises a relatively rigid three-dimensional interlocking skeletal framework of fibrous crystals formed during processing with a crystallizing agent. The solid soluble compositions of the present invention have a crystallizing agent and a low water content, and are readily soluble in an aqueous environment.

[0023] The present invention may be more readily understood by reference to the following detailed description of exemplary compositions. It should be understood that the scope of the claims is not limited to the specific products, methods, conditions, devices or parameters described herein, and the terminology used herein is not intended to limit the invention protected by the claims.

[0024] As used herein, a "solid soluble composition" (SDC) comprises the crystallizing agent sodium fatty acid carboxylate (which, when properly processed, forms a crystalline network of interconnected fibers that readily dissolves at the target wash temperature), an optional active agent such as a fresh feel benefit agent, and 10% by weight or less of water in the form of solid particles during the initial mixing stage.

[0025] As used herein, a "PEG composition" (PEGC) comprises PEG and optionally a fresh feel benefit agent.

[0026] As used herein, "domain" means a continuous mass comprising substantially the same material. In one embodiment, the domain may include SDC; in another embodiment, the domain may include PEGC.

[0027] As used herein, "low moisture content composition" means a freshness feel composition comprising both domains of SDC and PEGC and a freshness feel benefit agent, and wherein the low moisture content composition has a moisture content of less than about 10% by weight.

[0028] "Consumer products" herein include purchased low-water compositions for at least partially dissolving and releasing one or more active agents. Such products include, but are not limited to: laundry cleaning compositions and detergents, fabric softening compositions, fabric enhancing compositions, fabric refreshing compositions, laundry pre-washes, laundry pre-treaters, laundry additives, spray-on products, dry cleaning agents or compositions, laundry rinse additives, washing additives, post-rinse fabric treatments, ironing aids, unit dose formulations, delayed delivery formulations, detergents contained on or in porous substrates or nonwoven sheets, and other suitable forms that may be apparent to those skilled in the art based on the teachings herein. Such products may be used as pre- and post-treatment agents for washing.

[0029] As used herein, "particles" means discrete masses (or blocks) in a low water content composition, typically with a mass greater than about 5 mg and a size greater than 1 mm. Particles can have different shapes, including but not limited to hemispherical, spherical, plate-like, jelly bear-shaped, and cashew-shaped. Particles can have one or more domains.

[0030] As used herein, a "solid soluble composition mixture" (SDCM) comprises the components of a solid soluble composition before water is removed (e.g., during a mixture stage or a crystallization stage). To produce a solid soluble composition, an intermediate solid soluble composition mixture is first formed that comprises an aqueous phase having an aqueous carrier. The aqueous carrier can be distilled water, deionized water, or tap water. The aqueous carrier can be present in an amount of about 65% to 99.5% by weight, alternatively about 65% to about 90% by weight, alternatively about 70% to about 85% by weight, alternatively about 75% by weight, based on the weight of the SDCM.

[0031] As used herein, "rheological solid composition" (RSC) describes the solid form of the SDCM after crystallization (crystallization stage) and before water is removed to obtain the SDC, wherein the RSC contains more than about 65% by weight water and the solid form results from the "structured" interlocking network (network microstructure) of fibrous crystalline particles from the crystallization agent.

[0032] As used herein, "PEG" includes polyethylene glycol (PEG) having a molecular weight of about 200 Daltons to about 50,000 Daltons, most preferably between about 6,000 Daltons and 10,000 Daltons.

[0033] As used herein and further described below, "freshness benefit agent" includes materials added to the fabric to impart a freshness benefit to the fabric through washing. In an embodiment, the freshness benefit agent can be a pure fragrance; in an embodiment, the freshness benefit agent can be an encapsulated fragrance (fragrance capsule); in an embodiment, the freshness benefit agent can be a mixture of fragrance and / or fragrance capsule.

[0034] As used herein, "crystallization temperature" describes the temperature at which a crystallization agent (or combination of crystallization agents) is completely dissolved in SDCM; alternatively, it describes the temperature at which a crystallization agent (or combination of crystallization agents) exhibits any crystallization in SDCM.

[0035] As used herein, "dissolution temperature" describes the temperature at which a low water content composition completely dissolves in water under normal washing conditions.

[0036] As used herein, "stable temperature" is the temperature at which most (or all) of the SDC domain material and / or the PEGC domain material completely melts, such that the composition no longer exhibits a stable solid structure and can be considered a liquid or paste, and the low water content composition no longer functions as expected. The stable temperature is the lowest temperature thermal transition determined by the "Thermal Stability Test Method". In embodiments of the present invention, the stable temperature may be greater than about 40°C, more preferably greater than about 50°C, more preferably greater than about 60°C, and most preferably greater than about 70°C to ensure stability in the supply chain. Those skilled in the art understand how to measure this lowest thermal transition with a differential scanning calorimetry (DSC) instrument.

[0037] As used herein, "humidity stability" is such a relative humidity: at this relative humidity, the low moisture content composition spontaneously absorbs more than 5% by weight of the initial mass of water from the humidity of the surrounding environment at 25°C. Water absorption can occur in the SDC domain and / or the PEGC domain. The absorption of small amounts of water when exposed to a humid environment can achieve a more sustainable packaging. The absorption of large amounts of water risks causing the composition to soften or liquefy, so that it can no longer function as expected. In embodiments of the present invention, the humidity stability may be higher than 70% RH, more preferably higher than 80% RH, more preferably higher than 90% RH, and most preferably higher than 95% RH. Those skilled in the art understand how to measure a 5% weight increase with a DVS (dynamic vapor sorption) instrument, which is further described in the "Humidity Test Method".

[0038] Unless otherwise specified, "cleaning compositions" as used herein include all-purpose or "heavy-duty" detergents in granular or powder form, especially cleaning detergents; all-purpose detergents in liquid, gel or paste form, especially the so-called heavy-duty liquid types; liquid fine fabric detergents; hand dishwashing detergents or light-duty dishwashing detergents, especially those of the high-sudsing type; machine dishwashing detergents, including various pouches, tablets, granules, liquids and rinse-aid types for home and institutional use; liquid cleaning and disinfecting agents, including antibacterial hand wash types, cleaning bars, mouthwashes, denture cleaners, dentifrices, car or carpet washes, bathroom cleaners; hair shampoos and hair rinses; shower gels and bubble baths and metal cleaners; and cleaning aids, such as bleach additives and "stain bars" or pre-treatment products carrying substrates, such as dryer-added papers, dry and moistened wipes and pads, nonwoven substrates and sponges; and sprays and aerosols.

[0039] As used herein, "dissolves during normal use" means that the low water content composition completely dissolves or substantially dissolves during use in an aqueous environment.

[0040] As used herein, the term "bio-based" material refers to a renewable material.

[0041] As used herein, the term "renewable material" refers to a material made from renewable resources. As used herein, the term "renewable resources" refers to a resource produced via a natural process at a rate equivalent to its consumption rate (e.g., within a 100-year period). The resource can be natural or replenished by agricultural technology. Non-limiting examples of renewable resources include plants (e.g., sugar cane, beet, corn, potato, citrus fruit, woody plants, lignocellulose, hemicellulose, fibrous waste), animals, fish, bacteria, fungi and forestry products. These resources can be naturally occurring, hybrids, or genetically engineered organisms. The formation of natural resources such as crude oil, coal, natural gas and peat requires more than 100 years, and they are not considered to be renewable resources. Since at least a portion of the material of the present invention derives from a renewable resource that can isolate carbon dioxide, the use of this material can reduce global warming potential, and reduce fossil fuel consumption.

[0042] As used herein, the term "biobased content" refers to the amount of carbon in a material that is derived from renewable resources as a percentage of the total organic carbon weight (mass) in the material as determined by ASTM D6866-10 Method B.

[0043] The term "solid" refers to the state of a low-water content composition under the conditions of expected storage and use of the composition.

[0044] As used herein, the articles including "a" and "an" when used in a claim should be understood to mean one or more of what is claimed or described.

[0045] As used herein, the terms "including," "comprising," and "containing" are intended to be non-limiting.

[0046] Unless otherwise indicated, all component or composition levels are in terms of the active portion of that component or composition and are exclusive of impurities, for example, residual solvents or by-products, which may be present in commercially available sources of such component or composition.

[0047] Unless otherwise indicated, all percentages and ratios are calculated by weight. Unless otherwise indicated, all percentages and ratios are calculated based on the total composition.

[0048] It should be understood that each maximum numerical limitation given throughout this specification includes each lower numerical limitation, as if such lower numerical limitations were expressly written herein. Each minimum numerical limitation given throughout this specification will include each higher numerical limitation, as if such higher numerical limitations were expressly written herein. Each numerical range given throughout this specification will include each narrower numerical range falling within such wider numerical range, as if such narrower numerical ranges were all expressly written herein.

[0049] Solid soluble composition (SDC) comprises fibrous interlocking crystals ( Figure 1A and Figure 1B ), these interlocking crystals have sufficiently large crystal fiber length and concentration to form a mesh microstructure. The mesh allows the SDC to be solid with a relatively small amount of material. The mesh also allows for the entrapment and protection of particulate active agents such as freshness benefit agents, such as fragrance capsules ( Figure 2A and Figure 2B ). In an embodiment, the active material is a discrete particle having a diameter of less than 100 μm, preferably less than 50 μm, more preferably less than 25 μm. In addition, the significant voids in the reticular microstructure also allow for the inclusion of liquid active agents such as freshness benefit agents, such as pure fragrances. In an embodiment, up to about 15% by weight of active agent, preferably between 13% and 0.5% by weight of active agent, preferably between 13% and 2% by weight of active agent, most preferably between 10% and 2% by weight of active agent may be added. These voids also provide a path for water to be entrained into the microstructure during washing to accelerate dissolution relative to completely solid compositions.

[0050] Surprisingly, SDC with high dissolution rate, low water content, moisture resistance and thermal stability can be prepared. The sodium salt of long-chain fatty acid (i.e., sodium myristate (NaCl4) to sodium stearate (NaCl8)) can form fibrous crystals. It is generally believed that the crystal growth pattern that leads to fibrous crystal habit reflects the hydrophilic (head group) and hydrophobic (hydrocarbon chain) balance of NaCl4-NaCl8 molecules. As disclosed in the present patent application, although the crystallizer used has the same contribution to hydrophilicity, they have extraordinarily different hydrophobic characteristics due to the shorter hydrocarbon chain of the fatty acid sodium carboxylate adopted. In fact, the carbon chain length is approximately half of the length of the previously disclosed carbon chain (US2021 / 0315783A1). In addition, those skilled in the art recognize that many surfactants (such as alkyl sulfates) are susceptible to significant humidity absorption and significant temperature-induced changes, thereby having the same chain, but having different head groups. The crystallizer group selected in the present invention can achieve all these useful properties.

[0051] Current water-soluble polymers (e.g., separate PEG) are limited to using encapsulated spices as a fragrance enhancer delivery system. Encapsulated spices are delivered in a water-based slurry, and the slurry is limited to containing at most 20% to 30% by weight of encapsulated spices, thereby limiting the total amount of encapsulated spices to about 1.2% by weight. Using an encapsulated fragrance content higher than these contents prevents the water-soluble carrier from solidifying, thereby limiting the delivery of encapsulated spices. As a result, consumers are generally only limited by the limitations of the materials they can add to the washing liquid to make the desired freshness level insufficient. Compared with current water-soluble polymers, the solid soluble composition of the present invention can constitute a component of up to about 18% by weight of the spice capsule, and produces about 15 times of the spice delivery amount. Such a high delivery amount is achieved at least in part by the low water content of the composition of the present invention, and this low water content allows the user to feel a significantly improved freshness ( Figure 3 ).

[0052] The improved performance of the compositions of the present invention compared to existing solid soluble compositions such as freshening laundry beads is believed to be associated with the dissolution rate of the composition matrix. Without being limited by theory, it is believed that if the composition dissolves later in the wash cycle, the encapsulated fragrance is more likely to be deposited on the fabric throughout the wash (TTW) to enhance the freshness performance. The water-soluble polymers currently used in commercially available fabric freshening beads have a limited dissolution rate, where the dissolution rate is set by the limited molecular weight (MW) range of the polyethylene glycol (PEG) used as the dissolution matrix. Therefore, a single PEG bead must work under a certain range of machine and washing conditions, thereby limiting performance. In contrast, by adjusting the ratio of the composition components (e.g., the ratio of sodium laurate (NaL) to sodium caprate (NaD)), the dissolution rate of the composition of the present invention can be adjusted under a certain range of machine and washing conditions ( FIG. 4A to FIG. 4C This allows the opportunity to create a wide range of compositions that can be used in many different wash conditions, where the SDC domains can release the freshness benefit agent at different times in the wash cycle.

[0053] The main commercially available fabric freshness bead preparation process limits the choice of freshness benefit agents; instead, SDC domains can be processed and added to low moisture content compositions. The PEG used to form most current commercial beads must be processed at temperatures above the PEG melting point (between 70°C and 80°C); preparing SDC domains at room temperature allows a wider variety of freshness technologies to be implemented. During implementation, the PEG melting point temperature must be maintained for several hours, and some fragrance raw materials are particularly volatile and therefore flash evaporate during processing. For SDC, the inclusion of fragrance oils is carried out at about 25°C, thereby widening the range of pure fragrance additions. In addition, many fragrance capsule wall constructions will fail at higher processing temperatures, thereby releasing the encapsulated fragrance and making it ineffective in low moisture content compositions. Processing in fragrance capsules at lower temperatures enables a wider range of capsules.

[0054] It is difficult to control water migration in mixed bead compositions (e.g., low and high moisture content beads) using currently used water-soluble polymers because water migrates to the surface of the high moisture content beads. Since the beads are typically packaged in closed packages that minimize moisture transfer into and out of the package, moisture trapped on the surface of the high moisture content beads contacts the surface of the low moisture content beads, causing bead agglomeration and product dispensing problems. In contrast, the structure of solid soluble compositions prevents water migration, thus enabling the use of materials that are sensitive to water absorption (e.g., cationic polymers, bleach).

[0055] As previously discussed, existing bead formulations use PEG (and other structural materials) that are susceptible to degradation when exposed to heat and / or humidity during shipping. To mitigate such degradation, special shipping conditions and / or packaging are often required. The SDC of the present invention has a crystalline structure that is stable over a range of temperature and humidity conditions. The SDC domain preferably exhibits %dm <5% at 70% RH, more preferably %dm <5% at 80% RH, and most preferably %dm <5% at 90% RH ( Figure 5 ), as determined by the Humidity Test Method; and substantially no melting transition at temperatures below 50°C, as determined by the Thermal Stability Test Method ( Figure 6 ). Therefore, no additional resources are required for refrigeration during transportation, nor for plastic packaging to prevent moisture transfer. The inclusion of SDC domains in low water content compositions enables robust protection of freshness benefit agents.

[0056] Finally, without wishing to be limited by theory, it is believed that the high dissolution rate of the solid soluble composition is provided at least in part by the reticular microstructure. This is believed to be important because it is this porous structure that provides the product with a "light feel", as well as the ability to dissolve rapidly relative to compressed tablets, which allows for immediate delivery of the active ingredient during use. It is believed to be important that a single crystallizing agent (or in combination with other crystallizing agents) forms fibers during the preparation of the solid soluble composition. Forming fibers allows the solid soluble composition to retain the active ingredient without the need for compression, which may destroy the microcapsules.

[0057] In an embodiment, the fibrous crystals may have a minimum length of 10 μm and a thickness of 2 μm as determined by the Fiber Test Method.

[0058] In embodiments, the active ingredient may be in the form of particles that may be: a) uniformly dispersed within the mesh microstructure; b) applied to the surface of the mesh microstructure; or c) partially dispersed within the mesh microstructure and partially applied to the surface of the mesh microstructure. In embodiments, the active ingredient may be: a) in the form of a soluble film on the top surface of the mesh microstructure; b) in the form of a soluble film on the bottom surface of the mesh microstructure; or c) in the form of a soluble film on both the bottom and top surfaces of the mesh microstructure. The active ingredient may be present as a combination of a soluble film and particles. Non-limiting examples of particles are presented in Figure 7 , Figure 8 , Fig. 9 and Fig.10 middle.

[0059] Crystallization agent

[0060] The crystallization agent is selected according to its ability to impart different properties to the SDC domain. The crystallization agent is selected from sodium carboxylates of small-group fatty acids with saturated chains and chain lengths ranging from C8 to C12. Within this composition range, using the preparation method described, such sodium carboxylates of fatty acids provide a fibrous network microstructure, an ideal solubilization temperature for dissolution in preparation and use, and through appropriate blending, the resulting solid soluble composition has adjustability in these properties for various uses and conditions.

[0061] Crystallization agent can be present in the solid soluble composition mixture for producing SDC domains in an amount of about 5 wt % to about 35 wt %, about 10 wt % to about 35 wt %, or about 15 wt % to about 35 wt %. Crystallization agent can be present in the SDC domain in an amount of about 50 wt % to about 99 wt %, about 60 wt % to about 95 wt %, about 70 wt % to about 90 wt %. Crystallization agent can be present in the low water content composition in an amount of about 5 wt % to about 60 wt %, about 10 wt % to about 50 wt %, about 15 wt % to about 40 wt %.

[0062] Suitable crystallizing agents include sodium caprylate (NaC8), sodium caprate (NaC10), sodium dodecanoate or sodium laurate (NaC12), and combinations thereof.

[0063] Capsule material

[0064] The capsule may include a wall material (active agent delivery capsule or simply "capsule") that encapsulates an active agent (described below) such as a freshness benefit agent. The freshness benefit agent may be referred to herein as a "benefit agent" or "encapsulated benefit agent". The encapsulated active agent is encapsulated in the core. The benefit agent may be at least one of: a fragrance mixture or a deodorant or a combination thereof. The benefit agent may include a material selected from the group consisting of: a fragrance raw material such as 3-(4-tert-butylphenyl)-2-methylpropanal, 3-(4-tert-butylphenyl)-propanal, 3-(4-isopropylphenyl)-2-methylpropanal, 3-(3,4-methylenedioxyphenyl)-2-methylpropanal and 2,6-dimethyl-5-heptanal, α-damascone, β-damascone, γ-damascone, β-damascone, 6,7-dihydro-1,1,2,3,3-pentamethyl-4(5H)-indanone, methyl-7,3-dihydro-2H-1,5-benzodioxin-3-one, 2-[2-(4-methyl-3-cyclohexenyl-1-yl)propyl]cyclopentan-2-one, 2-sec-butylcyclohexanone, and β-dihydroionone, linalool, ethyl linalool, tetrahydrolinalool and dihydromyrcenol; silicone oils, waxes such as polyethylene wax; essential oils such as fish oil, jasmine, camphor, lavender; skin coolants such as menthol, methyl lactate; vitamins such as vitamin A and vitamin E; sunscreens; glycerol; catalysts such as manganese catalysts or bleaching catalysts; bleaching agent particles such as perborate; silica particles; antiperspirant active substances; cationic polymers and mixtures thereof. Suitable benefit agents can be purchased from Givaudan Corp. (Mount Olive, New Jersey, USA), International Flavors & Fragrances Corp. (South Brunswick, New Jersey, USA), Firmenich (Geneva, Switzerland), or Encapsys (Appleton, Wisconsin, USA). As used herein, "fragrance raw materials" refers to one or more of the following ingredients: essential oils; aromatic compounds; materials provided together with essential oils, aromatic compounds, stabilizers, diluents, processing aids and contaminants; and any materials that normally accompany essential oils and aromatic compounds.

[0065] The wall (or shell) material of the active agent delivery capsule can include: melamine, polyacrylamide, silicone, silicon dioxide, polystyrene, polyurea, polyurethane, polyacrylate-based materials, polyacrylate-based materials, gelatin, styrene malic anhydride, polyamide, aromatic alcohols, polyvinyl alcohol, and mixtures thereof. Melamine wall materials can include melamine cross-linked with formaldehyde, melamine-dimethoxyethanol cross-linked with formaldehyde, and mixtures thereof. Polystyrene wall materials can include polystyrene cross-linked with divinylbenzene. Polyurea wall materials can include urea cross-linked with formaldehyde, urea cross-linked with glutaraldehyde, polyisocyanates reacted with polyamines, polyamines reacted with aldehydes, and mixtures thereof. Polyacrylate-based wall materials may include polyacrylates formed from methyl methacrylate / dimethylaminomethyl methacrylate, polyacrylates formed from amine acrylate and / or methacrylate and strong acids, polyacrylates formed from carboxylic acid acrylate and / or methacrylate monomers and strong bases, polyacrylates formed from amine acrylate and / or methacrylate monomers and carboxylic acid acrylate and / or carboxylic acid methacrylate monomers, and mixtures thereof.

[0066] The composition may include about 0.05% to about 20%, or about 0.05% to about 10%, or about 0.1% to about 5%, or about 0.2% to about 2% active agent delivery capsules by weight of the composition. The composition may include sufficient active agent delivery capsules to provide the composition with about 0.05% to about 10%, or about 0.1% to about 5%, or about 0.1% to about 2% of encapsulated active agent by weight of the composition, which encapsulated active agent may preferably be a fragrance raw material. When discussing the amount or weight percentage of active agent delivery capsules herein, it means the sum of wall material and core material.

[0067] Active agent delivery capsules according to the present disclosure may be characterized by a volume weighted median particle size of about 1 μm to about 100 μm, preferably about 10 μm to about 100 μm, preferably about 15 μm to about 50 μm, more preferably about 20 μm to about 40 μm, even more preferably about 20 μm to about 30 μm. Different particle sizes can be obtained by controlling the droplet size during emulsification.

[0068] The active agent delivery capsules may be characterized by a core to shell ratio of up to 99:1, or even 99.5:1, on a weight basis.

[0069] Wall materials based on polyacrylic acid esters may include polyacrylic acid esters formed from alkyl and / or glycidyl esters of acrylic acid and / or methacrylic acid, acrylates and / or methacrylates carrying hydroxyl and / or carboxyl groups, and allyl glucamide, and mixtures thereof.

[0070] Wall materials based on aromatic alcohols include aryloxyalkanols, arylalkanols and oligomeric alkanol aryl ethers. They may also contain aromatic compounds with at least one free hydroxyl group, particularly preferably at least two directly aromatically coupled free hydroxyl groups, wherein it is particularly preferred if at least two free hydroxyl groups are directly coupled to an aromatic ring and more particularly preferably positioned in the meta position relative to each other. Preferably, the aromatic alcohol is selected from phenol, cresols (o-cresol, m-cresol and p-cresol), naphthols (α-naphthol and β-naphthol) and thymol, as well as ethylphenol, propylphenol, fluorophenol and methoxyphenol.

[0071] The polyurea based wall material may comprise a polyisocyanate.

[0072] The polyvinyl alcohol-based wall material may comprise a cross-linked hydrophobically modified polyvinyl alcohol including a cross-linker comprising: i) a first dextran aldehyde having a molecular weight of 2,000 Da to 50,000 Da; and ii) a second dextran aldehyde having a molecular weight of greater than 50,000 Da to 2,000,000 Da.

[0073] The core of the active agent delivery capsule of the present disclosure may include a partitioning modifier, which can promote a more robust formation of the shell. The partitioning modifier can be combined with the fragrance oil material of the core before incorporation into the wall-forming monomer. The partitioning modifier can be present in the core at a content of about 5% to about 55%, preferably about 10% to about 50%, more preferably about 25% to about 50%, based on the weight of the core.

[0074] The distribution modifier may include a material selected from the group consisting of vegetable oils, modified vegetable oils, monoesters, diesters and triesters of C4-C24 fatty acids, isopropyl myristate, lauryl benzophenone, lauryl laurate, methyl behenate, methyl laurate, methyl palmitate, methyl stearate, and mixtures thereof. The distribution modifier may preferably include isopropyl myristate or even consist of isopropyl myristate. The modified vegetable oil may be esterified and / or brominated. The modified vegetable oil may preferably include castor oil and / or soybean oil. U.S. Patent Application Publication 20110268802, incorporated herein by reference, describes other distribution modifiers that may be used in the active agent delivery capsules of the present invention.

[0075] The active agent capsules may be coated with a deposition aid, a cationic polymer, a nonionic polymer, an anionic polymer or a mixture thereof. Suitable polymers may be selected from polyvinyl formaldehyde, partially hydroxylated polyvinyl formaldehyde, polyvinyl amine, polyethylene imine, ethoxylated polyethylene imine, polyvinyl alcohol, polyacrylate, and combinations thereof. The freshening composition may include one or more types of active agent delivery capsules, such as two types of active agent delivery capsules, wherein one of the first active agent delivery capsule or the second active agent delivery capsule (a) has a wall made of a different wall material than the other; (b) has a wall comprising a different amount of wall material or monomer than the other; or (c) contains a different amount of a fragrance oil component than the other; (d) contains different fragrance oils; (e) has a wall that is cured at different temperatures; (f) contains fragrance oils with different cLogP values; (g) contains fragrance oils with different volatilities; (h) contains fragrance oils with different boiling points; (i) has a wall made of wall materials with different weight ratios; (j) has a wall that is cured at different curing times; and (k) has a wall that is heated at different rates.

[0076] Preferably, the active agent capsule has a wall material comprising a polymer of acrylic acid or a derivative thereof, and a benefit agent comprising a fragrance mixture.

[0077] Pure spice ingredients

[0078] The solid soluble composition may include an unencapsulated perfume comprising one or more perfume raw materials that provide only hedonic benefits (i.e., not neutralizing malodors, but providing a pleasant aroma). Suitable perfumes are disclosed in US 6,248,135. For example, the solid soluble composition may include a mixture of a volatile aldehyde for neutralizing malodors and a hedonic perfume aldehyde.

[0079] Water Phase

[0080] The aqueous phase present in the solid soluble composition mixture and the solid soluble composition consists of an aqueous carrier of water and optionally other minor ingredients including sodium chloride.

[0081] The aqueous phase can be present in the solid soluble composition mixture in an amount of about 65% to 95% by weight, about 65% to about 90% by weight, about 65% to about 85% by weight, based on the weight of the rheological solid formed as an intermediate composition after crystallization of the solid soluble composition mixture. The aqueous phase can be present in the solid soluble composition in an amount of 0% to about 10% by weight, 0% to about 9% by weight, 0% to about 8% by weight, or about 5% by weight, based on the weight of the intermediate rheological solid.

[0082] The sodium chloride in the aqueous phase solid soluble composition mixture can be present in an amount between 0 wt % to about 10 wt %, between 0 wt % to about 5 wt %, or between 0 wt % to about 1 wt %. The sodium chloride in the solid soluble composition can be present in an amount between 0 wt % to about 50 wt %, between 0 wt % to about 25 wt %, or between 0 wt % to about 5 wt %. In embodiments, the SDC may contain less than 2 wt % sodium chloride to ensure humidity stability.

[0083] SDC Domain

[0084] The Solid Soluble Composition Domain consists essentially of the solid soluble compositions described herein.

[0085] In one embodiment, the SDC domain contains less than about 13 wt % pure fragrance; in another embodiment, the SDC domain contains between about 10 wt % and 1 wt % pure fragrance; in another embodiment, the SDC domain contains between about 8 wt % and 2 wt % pure fragrance, as exemplified by "% Freshener (Dry)" in the Examples.

[0086] In one embodiment, the SDC domain contains less than about 16 wt % of fragrance capsules; in another embodiment, the SDC domain contains between about 15 wt % and 1 wt % of fragrance capsules; in another embodiment, the SDC domain contains between about 15 wt % and 2 wt % of fragrance capsules; in another embodiment, the SDC domain contains between about 15 wt % and 5 wt % of fragrance capsules, as exemplified by "% Freshener (Dry)" in the Examples.

[0087] Active agent (active substance)

[0088] Other components can optionally be dissolved in the aqueous phase of the SDC. These combined components are referred to as active agents. Such active agents include, but are not limited to, fresh feel benefit agents (as previously described), fabric care actives, catalysts, activators, peroxides, enzymes, antimicrobial agents, preservatives, sodium chloride, surfactants, and polyols. Crystallizing agents and insoluble active agents can be dispersed in the aqueous phase.

[0089] Fabric Care Actives

[0090] In an embodiment, the active agent may include one or more fabric care actives (actives) that are at least one of the following: fabric softener actives, cationic polymers, dye transfer inhibitors, malodor control agents, and mixtures thereof. The fabric care actives may be of plant origin. The low moisture composition may contain from about 1% to about 50% by weight of fabric care actives, or even from about 1% to about 40%, or even from about 1% to about 25% by weight of fabric care actives. Similarly, the low moisture composition may contain from about 2% to about 50% by weight of fabric care actives, optionally from about 3% to about 30%, further optionally from about 5% to about 25% by weight of fabric care actives.

[0091] Fabric softener actives

[0092] The fabric care active agent may be a fabric softener active. The fabric softener may be a polysiloxane, a fabric softening clay, a cationic polymer or a mixture thereof. For example, the fabric softener active may be a polydimethylsiloxane.

[0093] The low-water composition may include a quaternary ammonium compound so that the low-water composition can provide a softening benefit to the washed fabrics throughout the wash period, especially during the wash sub-cycle of a washing machine with a wash and rinse sub-cycle. The quaternary ammonium compound (quat) may be an ester quaternary ammonium compound. Suitable quaternary ammonium compounds include, but are not limited to, materials selected from the group consisting of or selected from or selected from at least one of: ester quaternary ammonium compounds, amide quaternary ammonium compounds, imidazoline quaternary ammonium compounds, alkyl quaternary ammonium compounds, amide ester quaternary ammonium compounds, and combinations thereof. Suitable ester quaternary ammonium compounds include, but are not limited to, materials that are at least one of: monoester quaternary ammonium compounds, diester quaternary ammonium compounds, triester quaternary ammonium compounds, or combinations thereof.

[0094] The low water content composition may include about 5% to about 45% of a quaternary ammonium compound by weight of the low water content composition. The quaternary ammonium compound may optionally have an iodine value of about 18 to about 60, optionally about 18 to about 56, optionally about 20 to about 60, optionally about 20 to about 56, optionally about 20 to about 42, and any integer in the aforementioned range. Optionally, the low water content composition may include about 10% to about 40% of a quaternary ammonium compound by weight of the low water content composition, and optionally have an iodine value in any of the above ranges. Optionally, the low water content composition may include about 20% to about 40% of a quaternary ammonium compound by weight of the low water content composition, and optionally have an iodine value in the above range.

[0095] The quaternary ammonium compound may be at least one of the following: an ester of bis-(2-hydroxypropyl)-dimethylammonium methyl sulfate, an isomer of an ester of bis-(2-hydroxypropyl)-dimethylammonium methyl sulfate and a fatty acid, N,N-bis-(stearoyl-2-hydroxypropyl)-N,N-dimethylammonium methyl sulfate, an ester of bis-(2-hydroxypropyl)-dimethylammonium methyl sulfate, an isomer of an ester of bis-(2-hydroxypropyl)-dimethylammonium methyl sulfate, an ester of N,N-bis(hydroxyethyl)-N,N-dimethylammonium chloride, an ester of N,N-bis(stearoyl-oxyethyl)-N,N-dimethylammonium chloride, an ester of N,N,N-tris(2-hydroxyethyl)-N-methylammonium methyl sulfate, N,N-bis-(palmitoyl-2-hydroxypropyl)- )-N,N-dimethyl ammonium methyl sulfate, N,N-bis-(stearoyl-2-hydroxypropyl)-N,N-dimethyl ammonium chloride, 1,2-di-(stearoyloxy)-3-trimethylpropyl ammonium chloride, canola oil dimethyl ammonium chloride, di(hard) tallow oil dimethyl ammonium chloride, canola oil dimethyl ammonium methyl sulfate, 1-methyl-1-stearoylaminoethyl-2-stearoyl imidazoline methyl ester sulfate, imidazoline quaternary ammonium salt (no longer used by P&G): 1-tallowamidoethyl-2-tallowoylimidazoline, dipalmitoylmethylhydroxyethyl ammonium methyl sulfate, dipalmitoylmethylhydroxyethyl ammonium methyl sulfate, 1,2-di(acyloxy)-3-trimethylpropyl ammonium chloride or mixtures thereof.

[0096] Quaternary ammonium compounds may include compounds of the formula:

[0097] {R 2 4-m -N + -[XYR 1 ] m} - (1)

[0098] in:

[0099] m is 1, 2, or 3, provided that the value of each m is the same;

[0100] Each R 1 are independently a hydrocarbyl or substituted hydrocarbyl group;

[0101] Each R 2 is independently a C1-C3 alkyl or hydroxyalkyl group, preferably R 2 Selected from methyl, ethyl, propyl, hydroxyethyl, 2-hydroxypropyl, 1-methyl-2-hydroxyethyl, poly (C 2-3- alkoxy), polyethoxy, benzyl;

[0102] Each X is independently (CH2)n, CH2-CH(CH3)- or CH-(CH3)-CH2- and

[0103] Each n is independently 1, 2, 3 or 4, preferably each n is 2;

[0104] Each Y is independently -O-(O)C- or -C(O)-O-;

[0105] A- is independently selected from the group consisting of or selected from the following or selected from at least one of the following: chloride, methyl sulfate, ethyl sulfate and sulfate, preferably A- is selected from the group consisting of or selected from the following or selected from at least one of the following: chloride and methyl sulfate;

[0106] The prerequisite is that when Y is -O-(O)C-, each R 1 The total number of carbon atoms in the formula (C) is 13 to 21. Preferably, when Y is -O-(O)C-, each R 1 The total number of carbon atoms is 13 to 19.

[0107] Quaternary ammonium compounds may include compounds of the formula:

[0108] [R3N+CH2CH(YR1)(CH2YR1)]X-

[0109] wherein each Y, R, R1 and X- have the same meaning as above. Such compounds include those having the following formula:

[0110] [CH3]3N(+)[CH2CH(CH2O(O)CR1)O(O)CR1]C1(-) (2) wherein each R is methyl or ethyl, and each R1 is preferably in the range of C15 to C19. As used herein, when a diester is specified, it may include the monoester present.

[0111] An example of a preferred DEQA (2) is a "propyl" esterquat fabric softener active having the formula 1,2-di(acyloxy)-3-trimethylpropylammonium chloride. A third type of preferred fabric softening active has the formula:

[0112]

[0113] wherein each R, R1 and A- have the definitions given above; each R2 is a C1-6 alkylene group, preferably an ethylene group; and G is an oxygen atom or a -NR- group;

[0114] Quaternary ammonium compounds may include compounds of the formula:

[0115]

[0116] wherein R1, R2 and G are as defined above.

[0117] The quaternary ammonium compound may include a compound that is, for example, a condensation reaction product of a fatty acid and a dialkylene triamine in a molecular ratio of about 2:1, the reaction product comprising a compound of the formula:

[0118] R1-C(O)-NH-R2-NH-R3-NH-C(O)-R1 (5)

[0119] wherein R1, R2 are as defined above, and each R3 is C1-6 alkylene, optionally ethylene, and wherein the reaction product may be optionally quaternized by adding an alkylating agent such as dimethyl sulfate.

[0120] Quaternary ammonium compounds may include compounds of the formula:

[0121]

[0122] wherein R, R1, R2, R3 and A- are as defined above;

[0123] The quaternary ammonium compound may include a compound that is the reaction product of a fatty acid and a hydroxyalkyl alkylene diamine in a molecular ratio of about 2:1, the reaction product comprising a compound of the formula:

[0124] R1-C(O)-NH-R2-N(R3OH)-C(O)-R1 (7)

[0125] wherein R1, R2 and R3 are as defined above;

[0126] An eighth type of preferred fabric softening active has the formula:

[0127]

[0128] wherein R, R1, R2 and A- are as defined above.

[0129] Non-limiting examples of compound (1) are N,N-bis(stearoyloxyethyl)-N,N-dimethylammonium chloride, N,N-bis(tallowyloxyethyl)-N,N-dimethylammonium chloride, and N,N-bis(stearoyloxyethyl)-N-(2-hydroxyethyl)-N-methylammonium methyl sulfate.

[0130] A non-limiting example of compound (2) is 1,2-di(stearoyloxy)-3-trimethylpropylammonium chloride.

[0131] A non-limiting example of compound (3) is 1-methyl-1-stearoylaminoethyl-2-stearoyl imidazolinium methyl ester sulfate, commercially available from Witco Corporation under the trade name VARISOFT, wherein R1 is an acyclic aliphatic C15-C17 hydrocarbon group, R2 is an ethylene group, G is an NH group, R5 is a methyl group, and A- is a methyl sulfate anion.

[0132] A non-limiting example of compound (4) is 1-tallowylaminoethyl-2-tallowyl imidazoline, wherein R1 is an acyclic aliphatic C15-C17 hydrocarbon group, R2 is an ethylene group, and G is an NH group.

[0133] A non-limiting example of compound (5) is the reaction product of a fatty acid and diethylenetriamine in a molecular ratio of about 2:1, the reaction product mixture comprising a ",N"-dialkyldiethylenetriamine having the formula:

[0134] R1-C(O)-NH-CH2CH2-NH-CH2CH2-NH-C(O)-R1 wherein R1-C(O) is a commercially available alkyl group derived from a fatty acid of plant or animal origin (such as EMERSOL 223LL or EMERSOL 7021 available from Henkel Corporation), and R2 and R3 are divalent ethylene groups.

[0135] A non-limiting example of compound (6) is a difatty amidoamine-based softener having the following formula:

[0136] [R1-C(O)-NH-CH2CH2-N(CH3)(CH2CH2OH)-CH2CH2-NH-C(O)-R1]+

[0137] CH3SO4-

[0138] Wherein R1-C(O) is an alkyl group, the softener is commercially available, for example, from Witco Corporation under the trade name VARISOFT 222LT.

[0139] An example of compound (7) is the reaction product of a fatty acid and N-2-hydroxyethylethylenediamine in a molecular ratio of about 2:1, the reaction product mixture comprising a compound of the formula:

[0140] R1-C(O)-NH-CH2CH2-N(CH2CH2OH)-C(O)-R1

[0141] wherein R1-C(O) is a commercially available alkyl group derived from a fatty acid of plant or animal origin, such as EMERSOL 223LL or EMERSOL 7021 available from Henkel Corporation.

[0142] An example of compound (8) is a diquaternary ammonium compound having the following formula:

[0143]

[0144] Wherein R1 is derived from a fatty acid and the compound is commercially available from Witco Company.

[0145] The quaternary ammonium compound may be di-(tallowyloxyethyl)-N,N-methylhydroxyethyl ammonium methyl sulfate.

[0146] It will be appreciated that combinations of the quaternary ammonium compounds disclosed above are suitable for use in the present invention.

[0147] In the cationic nitrogenous salts herein, the anion A- is any anion compatible with the softener that provides electrical neutrality. Most commonly, the anions used to provide electrical neutrality in these salts come from strong acids, especially halides, such as chloride, bromide, or iodide. However, other anions, such as methyl sulfate, ethyl sulfate, acetate, formate, sulfate, carbonate, etc., may be used. Chloride and methyl sulfate may be anions A. Anions may also be doubly charged, in which case A- represents half a group.

[0148] The low moisture content composition may comprise from about 10% to about 40% by weight of the quaternary compound.

[0149] The iodine value of a quaternary ammonium compound is that of the parent fatty acid from which the compound is formed and is defined as the number of grams of iodine which react with 100 grams of the parent fatty acid from which the compound is formed.

[0150] First, the quaternary ammonium compound is hydrolyzed according to the following protocol: 25 g of the quaternary ammonium compound is mixed with 50 mL of water and 0.3 mL of sodium hydroxide (50% active). The mixture is boiled on a hot plate for at least one hour while avoiding the mixture from drying out completely. After one hour, the mixture is cooled and the pH is adjusted to neutral (pH between 6 and 8) with 25% sulfuric acid using pH test strips or a calibrated pH electrode.

[0151] Next, extract fatty acids from the mixture via liquid-liquid extraction acidified with hexane or petroleum ether: dilute the sample mixture to 160mL with water / ethanol (1:1) in an extraction cylinder, add 5 grams of sodium chloride, 0.3mL sulfuric acid (25% activity) and 50mL hexane. Stopper the cylinder and shake for at least 1 minute. Then, allow the cylinder to stand until 2 layers are formed. The top layer containing the fatty acid hexane solution is transferred to another container. Then use a hot plate to evaporate the hexane, leaving the extracted fatty acids.

[0152] Next, the iodine value of the parent fatty acid forming the fabric softening active substance is determined according to ISO3961:2013. The method for calculating the iodine value of the parent fatty acid includes dissolving a predetermined amount (0.1-3g) in 15mL chloroform. Then the dissolved parent fatty acid is reacted with 25mL acetic acid solution (0.1M) of iodine monochloride. 20mL 10% potassium iodide solution and 150mL deionized water are added thereto. After the halogen has been added, the excess iodine monochloride is determined by titrating with sodium thiosulfate solution (0.1M) in the presence of blue starch indicator powder. At the same time, the blank is determined under the same conditions with the same amount of reagent. The difference between the volume of sodium thiosulfate used in the blank and the volume of sodium thiosulfate used in the reaction with the parent fatty acid can calculate the iodine value.

[0153] The quaternary ammonium compound may be those used as part of BOUNCE dryer paper available from The Procter & Gamble Company, Cincinnati, Ohio, USA. The quaternary ammonium compound may be the reaction product of triethanolamine quaternized with dimethyl sulfate and partially hydrogenated tallow acid.

[0154] The fabric softening active may be of plant origin.For example, the fabric softening active may be selected from the group consisting of or selected from or selected from at least one of: aloe vera, coconut oil, glycerine, and mixtures thereof.

[0155] The low moisture composition may comprise from about 0.1% to about 50%, optionally from about 0.1% to about 40%, optionally from about 0.1% to about 20%, optionally from about 0.1% to about 15%, optionally from about 0.1% to about 12%, optionally from about 1% to about 15%, optionally from about 2% to about 20%, optionally from about 8% to about 10% by weight of fabric softening active.

[0156] Cationic polymers

[0157] The fabric care active may be a cationic polymer.The cationic polymer may provide the benefit of a deposition aid which aids the deposition of the quaternary ammonium compound onto the fabric and possibly some other benefit agent included in the low moisture content composition.

[0158] The low water content composition may contain from about 0.5% to about 10% of the cationic polymer by weight of the low water content composition. Optionally, the low water content composition may contain from about 0.5% to about 5% of the cationic polymer by weight of the low water content composition, or even from about 1% to about 5% by weight of the low water content composition, or even from about 2% to about 4% of the cationic polymer by weight of the low water content composition, or even about 3% of the cationic polymer by weight of the low water content composition. Without being bound by theory, it is believed that the cleaning performance of the laundry detergent in the wash decreases as the cationic polymer content in the low water content composition increases, and the acceptable cleaning performance of the detergent can be maintained within the above range.

[0159] The cationic polymer may have a cationic charge density of more than about 0.05 meq / g (meq means milliequivalent) to 23 meq / g, preferably from about 0.1 meq / g to about 4 meq / g, even more preferably from about 0.1 meq / g to about 2 meq / g, and most preferably from 0.1 meq / g to about 1 meq / g.

[0160] The cationic charge density mentioned above can be a pH of about 3 to about 9, optionally about 4 to about 9, at the pH of the intended use. The cationic charge density of a polymer refers to the ratio of the number of positive charges on the polymer to the molecular weight of the polymer. The charge density is calculated by dividing the net number of charges per repeating unit by the molecular weight of the repeating unit. The positive charge can be located on the polymer backbone and / or on the polymer side chains. The average molecular weight of such a suitable cationic polymer can generally be between about 10,000 and about 10 million, or even between about 50,000 and about 5 million, or even between about 100,000 and about 3 million.

[0161] Non-limiting examples of cationic polymers are cationic or amphoteric polysaccharides, proteins and synthetic polymers. Cationic polysaccharides include cationic cellulose derivatives, cationic guar gum derivatives, chitosan and its derivatives and cationic starch. Cationic polysaccharides have a molecular weight of about 1,000 to about 2 million, preferably about 100,000 to about 800,000. Suitable cationic polysaccharides include cationic cellulose ethers, especially cationic hydroxyethyl cellulose and cationic hydroxypropyl cellulose. Particularly preferred are cationic cellulose polymers with substituted anhydroglucose units corresponding to the following general structural formula:

[0162]

[0163] Where R 1 , R 2 , R 3 Each independently selected from H, CH3, C 8-24 Alkyl (straight or branched chain), or a mixture thereof;

[0164] R 4 For H,

[0165] n is from about 1 to about 10;

[0166] Rx is selected from H, CH3, C 8-24 Alkyl (straight or branched chain), or a mixture thereof, wherein Z is a water-soluble anion, preferably chloride and / or bromide; R 5 H, CH3, CH2CH 3、 or a mixture thereof; R 7 CH3, CH2CH3, phenyl, C 8-24 Alkyl (straight or branched), or mixtures thereof; and

[0167] R 8 and R 9 Each is independently CH3, CH2CH3, phenyl, or a mixture thereof:

[0168] The prerequisite is that the R of each anhydroglucose unit 1 , R 2 , R 3 At least one of the groups is And each polymer has at least one Group.

[0169] The charge density (defined by the number of cationic charges per 100 anhydroglucose units) of the cationic cellulose herein is preferably from about 0.5% to about 60%, more preferably from about 1% to about 20%, and most preferably from about 2% to about 10%.

[0170] The alkyl substitution on the anhydroglucose rings of the polymer ranges from about 0.01% to 5% per glucose unit of the polymeric material, more preferably from about 0.05% to 2% per glucose unit.

[0171] When added to water at room temperature, cationic cellulose may be lightly cross-linked with a dialdehyde, such as glyoxyl, to prevent the formation of lumps, agglomerates, or other agglomerates.

[0172] Examples of cationic hydroxyalkylcelluloses include those having the INCI name Polyquaternium 10, such as those sold under the trade names UCARE POLYMER JR 30M, JR 400, JR 125, LR 400, and LK 400, POLYMER PK polymers; Polyquaternium 67, such as those sold under the trade name SOFTCAT SK TM, all sold by Dow Chemicals, Midland MI; and Polyquaternium 4, such as those sold under the trade names CELQUAT H200 and CELQUAT L-200 from National Starch and Chemical Company (Bridgewater, NJ). Other suitable polysaccharides include those with glycidyl C 12 -C 22 Hydroxyethylcellulose or hydroxypropylcellulose quaternized with alkyl dimethyl ammonium chloride. Examples of such polysaccharides include polymers having the INCI name Polyquaternium 24, such as those sold by Dow Chemicals (Midland, MI) under the trade name QUATERNIUM LM 200. Cationic starch refers to starch that has been chemically modified to provide a starch with a net positive charge in a pH 3 aqueous solution. This chemical modification includes, but is not limited to, the addition of amino and / or ammonium groups to the starch molecule. Non-limiting examples of these ammonium groups may include substituents such as trimethyl hydroxypropyl ammonium chloride, dimethyl stearyl hydroxypropyl ammonium chloride, or dimethyl dodecyl hydroxypropyl ammonium chloride. The source of starch prior to chemical modification may be selected from a variety of sources, including tubers, legumes, cereals, and grains. Non-limiting examples of starch from this source may include corn starch, wheat starch, rice starch, waxy corn starch, oat starch, tapioca starch, waxy barley starch, waxy rice starch, gluten rice starch, glutinous rice starch, amylopectin, potato starch, tapioca starch, oat starch, sago starch, sweet rice starch, or mixtures thereof. Non-limiting examples of cationic starch include cationic corn starch, cationic tapioca starch, cationic potato starch, or mixtures thereof. Cationic starch may contain amylase, amylopectin, or maltodextrin. Cationic starch may include one or more additional modifications. For example, these modifications may include cross-linking, stability reactions, phosphorylation, hydrolysis, cross-linking. Stability reactions may include alkylation and esterification. Cationic starch suitable for use in the compositions of the present invention may be obtained under the trade name Commercially available from Cerestar, and commercially available from National Starch and Chemical Company under the trade name CATO 2A. Cationic galactomannans include cationic guar gum or cationic locust bean gum. Examples of cationic guar gums are quaternary ammonium derivatives of hydroxypropyl guar gum, such as those sold under the trade names JAGUAR C13 and JAGUAR EXCEL by Rhodia, Inc. (Cranbury, NJ) and N-HANCE by Aqualon (Wilmington, DE).

[0173] Other suitable cationic polymers for low water content compositions include polysaccharide polymers, cationic guar gum derivatives, cellulose ethers containing quaternary nitrogen, synthetic polymers, copolymers of etherified cellulose, guar gum, and starch. When used, the cationic polymers herein are soluble in the composition used to form the low water content composition, or are soluble in the complex coacervate phase in the composition forming the low water content composition. Suitable cationic polymers are described in U.S. Pat. Nos. 3,962,418, 3,958,581, and U.S. Publication No. 2007 / 0207109A1.

[0174] One class of suitable cationic polymers includes those prepared by polymerization of ethylenically unsaturated monomers using a suitable initiator or catalyst, such as those disclosed in WO 00 / 56849 and USPN 6,642,200. Suitable cationic polymers may be selected from the group consisting of synthetic polymers prepared by polymerization of one or more cationic monomers and optionally a second monomer, the cationic monomer being selected from the group consisting of or selected from the following or selected from at least one of the following: N,N-dialkylaminoalkyl acrylates, N,N-dialkylaminoalkyl methacrylates, N,N-dialkylaminoalkyl acrylamides, N,N-dialkylaminoalkyl methacrylamides, quaternized N,N-dialkylaminoalkyl acrylates, quaternized N,N-dialkylaminoalkyl methacrylates, quaternized N,N-dialkylaminoalkyl acrylamides, quaternized N,N-dialkylaminoalkyl methacrylamides, methacrylic acids The present invention relates to acrylamidopropyl-pentamethyl-1,3-propene-2-ol-dichloridum, N,N,N,N',N',N",N"-heptamethyl-N"-3-(1-oxy-2-methyl-2-propenyl)aminopropyl-9-oxy-8-azo-decane-1,4,10-trichloridum, vinylamine and its derivatives, allylamine and its derivatives, vinylimidazole, quaternized vinylimidazole and diallyldialkylammonium chloride and combinations thereof, wherein the second monomer is selected from the group consisting of or selected from the following or selected from at least one of the following: acrylamide, N,N-dialkylacrylamide, methacrylamide, N,N-dialkylmethacrylamide, acrylic acid C1-C12 Alkyl esters, acrylic acid C1-C 12 Hydroxyalkyl esters, polyalkylene glycol acrylates, C1-C methacrylate 12 Alkyl esters, methacrylate C1-C 12 Hydroxyalkyl esters, polyalkylene glycol methacrylates, vinyl acetate, vinyl alcohol, vinyl formamide, vinyl acetamide, vinyl alkyl ethers, vinyl pyridine, vinyl pyrrolidone, vinyl imidazole, vinyl caprolactam and derivatives, acrylic acid, methacrylic acid, maleic acid, vinyl sulfonic acid, styrene sulfonic acid, acrylamidopropyl methanesulfonic acid (AMPS) and their salts. The polymer may optionally be branched or crosslinked by using branching and crosslinking monomers. Branching and crosslinking monomers include ethylene glycol diacrylate, divinylbenzene and butadiene. Polyethyleneimines suitable for use herein are those sold under the trade name LUPASOL by BASF AG (Lugwigschaefen, Germany).

[0175] On the other hand, the cationic polymer can be at least one of the following: a cationic polysaccharide, polyethyleneimine and its derivatives, poly(acrylamide-co-diallyldimethylammonium chloride), poly(acrylamide-methacrylamidopropyltrimethylammonium chloride), poly(acrylamide-co-N,N-dimethylaminoethyl acrylic acid) and its quaternized derivatives, poly(acrylamide-co-N,N-dimethylaminoethyl methacrylate) and its quaternized derivatives, poly(hydroxyethyl acrylate-co-dimethylaminoethyl methacrylate), poly(hydroxypropyl acrylate-co-dimethylaminoethyl methacrylate), poly(hydroxypropyl acrylate-co-methacrylamidopropyltrimethylammonium chloride), poly(acrylamide-co-diallyldimethylammonium chloride-co-acrylic acid), poly(acrylamide-methacrylamidopropyltrimethylammonium chloride-co-acrylic acid), poly(diallyldimethylammonium chloride), poly(ethylene) poly(vinylpyrrolidone-co-dimethylaminoethyl methacrylate), poly(ethyl methacrylate-co-quaternized dimethylaminoethyl methacrylate), poly(ethyl methacrylate-co-oleyl methacrylate-co-diethylaminoethyl methacrylate), poly(diallyldimethylammonium chloride-co-acrylic acid), poly(vinylpyrrolidone-co-quaternized vinylimidazole), and poly(acrylamide-co-methacrylamidopropylpentamethyl- 1,3-propylene-2-ol diammonium chloride), suitable cationic polymers include polyquaternium-1, polyquaternium-5, polyquaternium-6, polyquaternium-7, polyquaternium-8, polyquaternium-10, polyquaternium-11, polyquaternium-14, polyquaternium-22, polyquaternium-28, polyquaternium-30, or polyquaternium-32, and polyquaternium-33, which are named according to the "International Nomenclature for Cosmetic Ingredients".

[0176] On the other hand, cationic polymers may include polyethyleneimine or polyethyleneimine derivatives. On the other hand, cationic polymers may include cationic polymers based on acrylic acid. On the other hand, cationic polymers may include cationic polyacrylamide. On the other hand, cationic polymers may include polymers comprising polyacrylamide and polymethacrylamidopropyltrimethylammonium cations. On the other hand, cationic polymers may include poly (acrylamide-N-dimethylaminoethyl acrylate) and quaternized derivatives thereof. In this regard, cationic polymers may be those sold under the trade name SEDIPUR purchased from BTC Specialty Chemicals (BASF Group, Florham Park, NJ). On the other hand, cationic polymers may include poly (acrylamide-co-methacrylamidopropyltrimethylammonium chloride). On the other hand, cationic polymers may include polymers not based on acrylamide, such as those sold under the trade name RHEOVIS CDE purchased from Ciba Specialty Chemicals (BASF Group, Florham Park, NJ), or as disclosed in U.S. Patent Publication 2006 / 0252668.

[0177] In another aspect, the cationic polymer can be selected from the group consisting of or selected from the following or selected from at least one of the following: cationic polysaccharides. In one aspect, the cationic polymer can be selected from the group consisting of or selected from the following or selected from at least one of the following: cationic cellulose ethers, cationic galactomannans, cationic guar gum, cationic starches, and combinations thereof.

[0178] Another class of suitable cationic polymers may include alkylamine-epichlorohydrin polymers, which are reaction products of amines and oligoamines with epichlorohydrin. Examples include dimethylamine-epichlorohydrin-ethylenediamine available under the trade names CARTAFIX CB, CARTAFIX TSF from Clariant (Basle, Switzerland).

[0179] Another group of suitable synthetic cationic polymers may include polyamidoamine-epichlorohydrin (PAE) resins of polyalkylene polyamines and polycarboxylic acids. The most commonly used PAE resins are condensation products of diethylenetriamine reacted with adipic acid followed by reaction with epichlorohydrin. They are available under the trade name KYMENE from Hercules Inc. (Wilmington DE) or under the trade name LURESIN from BASF AG (Ludwigshafen, Germany).

[0180] Cationic polymers may contain charge-neutralizing anions so that the entire polymer is neutral under ambient conditions. Non-limiting examples of suitable counterions (in addition to anionic species generated during use) include chloride, bromide, sulfate, methylsulfate, sulfonate, mesylate, carbonate, bicarbonate, formate, acetate, citrate, nitrate, and mixtures thereof.

[0181] The cationic polymer may have a weight average molecular weight of from about 500 Daltons to about 5,000,000 Daltons as determined by size exclusion chromatography with RI detection relative to polyethylene oxide standards.

[0182] or from about 1,000 Daltons to about 2,000,000 Daltons, or from about 5000 Daltons to about 1,000,000 Daltons. In one aspect, the cationic polymer may have a weight average molecular weight of from about 100,000 Daltons to about 800,000 Daltons.

[0183] The cationic polymer may be a plant-based cationic polymer. For example, the cationic polymer may be at least one of the following: cationic cyclodextrin, cationic cellulose, cationic gelatin, cationic dextran, cationic chitosan, or a mixture thereof.

[0184] The cationic polymer may be provided in a powder form. The cationic polymer may be provided in an anhydrous state.

[0185] The low moisture content composition may comprise from about 0.1% to about 50%, optionally from about 0.1% to about 40%, optionally from about 0.1% to about 20%, optionally from about 1% to about 20%, optionally from about 0.1% to about 15%, optionally from about 0.1% to about 12%, optionally from about 1% to about 15%, optionally from about 2% to about 20%, optionally from about 8% to about 10%, of a cationic polymer, by weight of the low moisture content composition.

[0186] Dye transfer inhibitors

[0187] The low moisture compositions may contain dye transfer inhibiting agents.

[0188] The dye transfer inhibiting agent may be a graft copolymer.

[0189] The graft copolymer may comprise: (a) a polyalkylene oxide having a number average molecular weight of about 1000 Da to about 20000 Da and based on ethylene oxide, propylene oxide or butylene oxide; and (b) a vinyl ester derived from a saturated monocarboxylic acid containing 1 to 6 carbon atoms; wherein (a) and (b) are present in a weight ratio of (a):(b) of about 1:0.1 to about 1:2. The polyalkylene oxide may be based on ethylene oxide. The vinyl ester may be derived from a saturated monocarboxylic acid containing 1 to 3 carbon atoms. The vinyl ester is vinyl acetate or a derivative thereof. (a) and (b) may be present in a weight ratio of (a):(b) of about 1:0.1 to about 1:1.7. About 1 mol % to about 60 mol % of (b) may be hydrolyzed. The graft copolymer may be a graft copolymer VAc-gPEG4000 purchased from BASF, Ludwigshafen, Germany. The synthesis of the graft copolymer VAc-gPEG4000 is described in WO 01 / 05874.

[0190] The graft copolymer may comprise (a) a polyalkylene oxide having a number average molecular weight of about 1000 Da to about 20000 Da and based on ethylene oxide, propylene oxide or butylene oxide; (b) N-vinyl pyrrolidone; and (c) a vinyl ester derived from a saturated monocarboxylic acid containing 1 to 6 carbon atoms; wherein (a) and (b) are present in a weight ratio of (a) to (b) of about 1:0.1 to about 1:1; wherein (a) is present in an amount greater than (c) by weight; wherein the order of addition of (b) and (c) in the graft polymerization is not important. The polyalkylene oxide may be based on ethylene oxide. The vinyl ester is derived from a saturated monocarboxylic acid containing 1 to 3 carbon atoms. The vinyl ester may be vinyl acetate or a derivative thereof. (a) and (b) may be present in a weight ratio of (a):(b) of about 1:0.2 to about 1:0.7. (a) and (c) may be present in a weight ratio of (a):(c) of about 1:0.1 to about 1:0.8. (b) and (c) may be present in a weight ratio of (b):(c) of about 1:0.1 to about 1:4. About 1 mol% to about 60 mol% of (c) may be hydrolyzed.

[0191] The low moisture content composition may comprise from about 0.1% to about 50%, optionally from about 0.1% to about 40%, optionally from about 0.1% to about 20%, optionally from about 1% to about 20%, optionally from about 0.1% to about 15%, optionally from about 0.1% to about 12%, optionally from about 1% to about 15%, optionally from about 2% to about 20%, optionally from about 8% to about 10% dye transfer inhibiting agent, by weight of the low moisture content composition.

[0192] Odor Control Agents

[0193] The fabric care active can be a malodor control agent. The malodor control agent can be any material capable of absorbing, containing, neutralizing, and or eliminating malodor. The malodor control agent can be at least one of the following: a host-guest compound, a malodor binding material, a malodor neutralizing material, or a combination thereof. The malodor control agent can be at least one of the following: α-cyclodextrin, an α-cyclodextrin derivative, β-cyclodextrin, a β-cyclodextrin derivative, γ-cyclodextrin, a γ-cyclodextrin derivative, δ-cyclodextrin, a δ-cyclodextrin derivative, a zinc salt of a C16-C18 fatty acid, or a mixture thereof.

[0194] The low moisture content composition may comprise from about 0.1% to about 20%, optionally from about 0.1% to about 15%, optionally from about 0.1% to about 12%, optionally from about 1% to about 15%, optionally from about 2% to about 20% of a malodor control agent by weight of the low moisture content composition.

[0195] catalyst

[0196] In an embodiment, the soluble active agent may include one or more metal catalysts. In an embodiment, the metal catalyst may include one or more of the following: dichloro-1,4-diethyl-1,4,8,11-tetraazabicyclo[6.6.2]hexadecanemanganese(II); and dichloro-1,4-dimethyl-1,4,8,11-tetraazabicyclo[6.6.2]hexadecanemanganese(II). In an embodiment, the non-metal catalyst may include one or more of the following: 2-[3-[(2-hexyldodecyl)oxy]-2-(sulfoxy)propyl]-3,4-dihydroisoquinolinium, inner salt; 3,4-dihydro-2-[3-[(2-pentylundecyl)oxy]-2-(sulfoxy)propyl]isoquinolinium, inner salt; 2-[3-[(2-butyldecyl)oxy]-2-(sulfoxy)propyl]-3,4-dihydroisoquinolinium, inner salt. Hydroisoquinolinium, inner salt; 3,4-dihydro-2-[3-(octadecyloxy)-2-(sulfooxy)propyl]isoquinolinium, inner salt; 2-[3-(hexadecyloxy)-2-(sulfooxy)propyl]-3,4-dihydroisoquinolinium, inner salt; 3,4-dihydro-2-[2-(sulfooxy)-3-(tetradecyloxy)propyl]isoquinolinium, inner salt; 2-[3-(dodecyloxy)-2-(sulfooxy)propyl]-3,4 -dihydroisoquinolinium, inner salt; 2-[3-[(3-hexyldecyl)oxy]-2-(sulfooxy)propyl]-3,4-dihydroisoquinolinium, inner salt; 3,4-dihydro-2-[3-[(2-pentylnonyl)oxy]-2-(sulfooxy)propyl]isoquinolinium, inner salt; 3,4-dihydro-2-[3-[(2-propylheptyl)oxy]-2-(sulfooxy)propyl]isoquinolinium, inner salt; 2-[3-[(2-butyl 2-[3-(decyloxy)-2-(sulfooxy)propyl]-3,4-dihydroisoquinolinium, inner salt; 3,4-dihydro-2-[3-(octyloxy)-2-(sulfooxy)propyl]isoquinolinium, inner salt; and 2-[3-[(2-ethylhexyl)oxy]-2-(sulfooxy)propyl]-3,4-dihydroisoquinolinium, inner salt.

[0197] Activator

[0198] In an embodiment, the soluble active agent may include one or more activators. In an embodiment, the activator may include one or more of the following: tetraacetylethylenediamine (TAED); benzoyl caprolactam (BzCL); 4-nitrobenzoyl caprolactam; 3-chlorobenzoyl caprolactam; benzoyloxybenzene sulfonate (BOBS); nonanoyloxybenzene sulfonate (NOBS); phenyl benzoate (PhBz); decanoyloxybenzene sulfonate (C 10-OBS); benzoyl valerolactam (BZVL); octanoyloxybenzenesulfonate (C8-OBS); perhydrolyzable esters; 4-[N-(nonanoyl)aminocaproyloxy]-benzenesulfonic acid sodium salt (NACA-OBS); dodecanoyloxybenzenesulfonate (LOBS or C 12 -OBS); 10-undecenoyloxybenzenesulfonate (UDOBS or C with unsaturation at position 10); 11 -OBS); decanoyloxybenzoic acid (DOBA); (6-octanoylaminohexanoyl)oxybenzenesulfonate; (6-nonanoylaminohexanoyl)oxybenzenesulfonate; and (6-decanoylaminohexanoyl)oxybenzenesulfonate.

[0199] Peroxycarboxylic acid

[0200] In an embodiment, the soluble active agent may comprise one or more preformed peroxycarboxylic acids. In an embodiment, the peroxycarboxylic acid may comprise one or more of the following: peroxymonosulfuric acid; perimidic acid; percarbonic acid; percarboxylic acids and salts of said acids; phthalimidoperoxycaproic acid; aminoperoxyacids; 1,12-diperoxydodecanedioic acid; and monoperoxyphthalic acid (hexahydrated magnesium salt), wherein the aminoperoxyacid may comprise N,N'-terephthaloyl-bis(6-aminocaproic acid), monononanamide of peroxysuccinic acid (NAPSA) or peroxyadipic acid (NAPAA), or N-nonanoylaminoperoxycaproic acid (NAPCA).

[0201] In an embodiment, the water-based and / or water-soluble benefit agent may include one or more diacyl peroxides. In an embodiment, the diacyl peroxide may include one or more of dinonanoyl peroxide, didecanoyl peroxide, didecanoyl peroxide, diundecanoyl peroxide, dilauroyl peroxide and dibenzoyl peroxide, di-(3,5,5-trimethylhexanoyl) peroxide, wherein the diacyl peroxide may be clathrate.

[0202] peroxide

[0203] In embodiments, the soluble active agent may include one or more hydrogen peroxides. In embodiments, the hydrogen peroxide source may include one or more of perborates, percarbonates, peroxyhydrates, peroxides, persulfates, and mixtures thereof, in one aspect, the hydrogen peroxide source may include sodium perborate, in one aspect, the sodium perborate may include monohydrate or tetrahydrate, sodium pyrophosphate peroxyhydrate, urea peroxyhydrate, trisodium phosphate peroxyhydrate, and sodium peroxide.

[0204] Enzymes

[0205] In embodiments, the soluble active agent may comprise one or more enzymes. In embodiments, the enzyme may comprise one or more of the following: peroxidase, protease, lipase, phospholipase, cellulase, cellobiohydrolase, cellobiose dehydrogenase, esterase, cutinase, pectinase, mannanase, pectate lyase, keratinase, reductase, oxidase, phenoloxidase, lipoxygenase, ligninase, pullulanase, tannase, pentosanase, glucanase, arabinosidase, hyaluronidase, chondroitinase, laccase, amylase and DNase.

[0206] Sensate

[0207] In an embodiment, the soluble active agent may include one or more components that provide a sensory benefit, commonly referred to as a sensory agent. The sensory agent may have sensory attributes, such as a sense of warmth, a tingling sensation, or a cool sensation. Suitable sensory agents include, for example, menthol, menthyl lactate, leaf alcohol, camphor, clove bud oil, eucalyptus oil, anethole, methyl salicylate, eucalyptol, cinnamon, 1-8 menthyl acetate, eugenol, oxanone, α-ionone, propenyl ethyl guaiacol, thymol, linalool, benzaldehyde, the cinnamaldehyde glycerol acetal called CGA, Winsense WS-5 provided by Renessenz-Symrise, the vanillyl butyl ether called VBE, and mixtures thereof.

[0208] In certain embodiments, the sensate includes a coolant. The coolant can be any of a variety of materials. Included in the present invention are amides, menthols, ketals, diols, and mixtures thereof. Some examples of amide coolants include, for example, p-menthane aminocarboxamide agents such as N-ethyl-p-menthane-3-carboxamide (commercially known as "WS-3"), N,2,3-trimethyl-2-isopropylbutanamide (known as "WS-23"), and N-(4-cyanomethylphenyl)-p-menthanecarboxamide (known as G-180 and supplied by Givaudan). G-180 is typically provided as a 7.5% solution in a flavor oil such as spearmint oil or peppermint oil. Examples of menthol coolants include, for example, menthol; 3-1-menthoxypropane-1,2-diol, known as TK-10, manufactured by Takasago; menthone glycerol acetal, known as MGA, manufactured by Symrise; and menthone glycerol acetal, known as G-180, manufactured by Symrise. As used herein, the terms menthol and menthyl include dextrorotatory and levorotatory isomers of these compounds and their racemic mixtures.

[0209] In certain embodiments, the sensate comprises a cooling agent selected from the group consisting of: menthol; 3-1-menthoxypropane-1,2-diol, menthyl lactate; N,2,3-trimethyl-2-isopropylbutanamide; N-ethyl-p-menthane-3-carboxamide; N-(4-cyanomethylphenyl)-p-menthanecarboxamide, and combinations thereof. In other embodiments, the sensate comprises menthol; N,2,3-trimethyl-2-isopropylbutanamide.

[0210] Surfactants

[0211] Detersive surfactant: Suitable detersive surfactants include anionic detersive surfactants, nonionic detersive surfactants, cationic detersive surfactants, zwitterionic detersive surfactants and amphoteric detersive surfactants and mixtures thereof. Suitable detersive surfactants may be linear or branched, substituted or unsubstituted, and may be derived from petrochemical materials or biomaterials. Preferred surfactant systems include anionic surfactants and nonionic surfactants, preferably in a weight ratio of 90:1 to 1:90. In some cases, a weight ratio of at least 1:1 anionic surfactant to nonionic surfactant is preferred. However, a ratio of less than 10:1 may be preferred. When present, the total surfactant level is preferably 0.1% to 60%, 1% to 50%, or even 5% to 40% by weight of the subject composition.

[0212] Anionic detersive surfactants: Anionic surfactants include, but are not limited to, those surface active compounds containing an organic hydrophobic group typically containing 8 to 22 carbon atoms or typically containing 8 to 18 carbon atoms in its molecular structure and at least one water solubilizing group preferably selected from sulfonates, sulfates and carboxylates to form a water soluble compound. Typically, the hydrophobic group includes a C8-C22 alkyl or acyl group. Such surfactants are used in the form of water soluble salts, and the salt-forming cation is typically selected from sodium, potassium, ammonium, magnesium and triethanolamine, with the sodium cation being the usual choice.

[0213] The anionic surfactants and auxiliary anionic co-surfactants of the present invention can exist in acid form, and the acid form can be neutralized to form a surfactant salt suitable for the composition of the present invention. Typical agents for neutralization include alkaline metal counterions such as hydroxides, such as NaOH or KOH. Other preferred agents for neutralizing the anionic surfactants of the present invention and auxiliary anionic surfactants or co-surfactants in acid form include ammonia, amines, oligoamines or alkanolamines. Alkanolamines are preferred. Suitable non-limiting examples include monoethanolamine, diethanolamine, triethanolamine, and other straight or branched alkanolamines known in the art; for example, highly preferred alkanolamines include 2-amino-1-propanol, 1-aminopropanol, monoisopropanolamine, or 1-amino-3-propanol. Amine neutralization can be completed in whole or in part, for example, a portion of the anionic surfactant mixture can be neutralized with sodium or potassium and a portion of the anionic surfactant mixture can be neutralized with amines or alkanolamines.

[0214] Suitable sulfonate detersive surfactants include methyl sulfonate, alpha olefin sulfonate, alkyl benzene sulfonate, especially alkyl benzene sulfonate, preferably C 10-13 Alkylbenzene sulfonates. Suitable alkylbenzene sulfonates (LAS) are available, preferably by sulfonating commercially available linear alkylbenzenes (LABs); suitable LABs include lower 2-phenyl LABs such as those sold under the trade name Those supplied by Sasol, or under the trade name Other suitable LABs include those supplied by Petresa, higher 2-phenyl LABs such as those sold under the trade name Those supplied by Sasol. Suitable anionic detersive surfactants are alkylbenzene sulfonates obtained by the DETAL catalyzed process, although other synthetic routes such as HF may also be suitable. In one aspect, the magnesium salt of LAS is used.

[0215] Suitable sulfate detersive surfactants include alkyl sulfates, preferably C 8-18 Alkyl sulfates, or mainly C 12 Alkyl sulfate.

[0216] Preferred sulfate detersive surfactants are alkyl alkoxylated sulfates, preferably alkyl ethoxylated sulfates, preferably C 8-18 Alkyl alkoxylated sulfate, preferably C 8-18 Alkyl ethoxylated sulfate, preferably alkyl alkoxylated sulfate having an average degree of alkoxylation of 0.5 to 20, preferably 0.5 to 10, preferably alkyl alkoxylated sulfate is C 8-18Alkyl ethoxylated sulfates having an average degree of ethoxylation of from 0.5 to 10, preferably from 0.5 to 5, more preferably from 0.5 to 3. The alkyl alkoxylated sulfates may have a broad alkoxy distribution or a peak alkoxy distribution.

[0217] Alkyl sulfates, alkyl alkoxylated sulfates and alkylbenzene sulfonates can be straight or branched, including 2-alkyl substituted or mid-chain branched types, substituted or unsubstituted, and can be derived from petrochemical materials or biomaterials. Preferably, the branching group is an alkyl group. Typically, the alkyl group is selected from methyl, ethyl, propyl, butyl, amyl, cyclic alkyl and mixtures thereof. Single or multiple alkyl branches may be present on the main hydrocarbon chain of the starting alcohol for preparing the sulfated anionic surfactant used in the composition of the present invention. Most preferably, the branched sulfated anionic surfactant is selected from alkyl sulfates, alkyl ethoxy sulfates and mixtures thereof.

[0218] Alkyl sulfates and alkyl alkoxy sulfates are commercially available with various chain lengths, ethoxylation and degree of branching. Commercially available sulfates include those based on Neodol alcohols from Shell company, Lial-Isalchem ​​and Safol from Sasol company, and natural alcohols from Procter & Gamble Chemicals company.

[0219] Other suitable anionic detersive surfactants include the alkyl ether carboxylates.

[0220] Nonionic detersive surfactant: Suitable nonionic detersive surfactants are selected from the group consisting of: C8-C 18 Alkyl ethoxylates, such as those available from Shell Nonionic surfactant; C6-C 12 Alkylphenol alkoxylates, wherein preferably the alkoxylate units are ethyleneoxy units, propyleneoxy units, or mixtures thereof; C 12 -C 18 Alcohol and C6-C 12 Condensates of alkylphenols with ethylene oxide / propylene oxide block polymers, such as those available from BASF Alkyl polysaccharides, preferably alkyl polyglycosides; methyl ester ethoxylates; polyhydroxy fatty acid amides; ether-terminated poly(alkoxylated) alcohol surfactants; and mixtures thereof.

[0221] Suitable nonionic detersive surfactants are alkyl polyglucosides and / or alkyl alkoxylated alcohols.

[0222] Suitable nonionic detersive surfactants include alkyl alkoxylated alcohols, preferably C 8-18Alkyl alkoxylated alcohol, preferably C 8-18 The alkyl ethoxylated alcohol, preferably the alkyl alkoxylated alcohol, has an average degree of alkoxylation of 1 to 50, preferably 1 to 30, or 1 to 20, or 1 to 10, preferably the alkyl alkoxylated alcohol is C 8-18 Alkyl ethoxylated alcohols having an average degree of ethoxylation of 1 to 10, preferably 1 to 7, more preferably 1 to 5, and most preferably 3 to 7. The alkyl alkoxylated alcohols may be linear or branched, and substituted or unsubstituted. Suitable nonionic surfactants include those sold under the trade name Those available from BASF.

[0223] Cationic detersive surfactants: Suitable cationic detersive surfactants include alkyl pyridinium compounds, alkyl quaternary ammonium compounds, alkyl quaternary phosphonium compounds, alkyl ternary sulfonium compounds, and mixtures thereof.

[0224] Preferred cationic detersive surfactants are quaternary ammonium compounds having the general formula:

[0225] (R)(R1)(R2)(R3)N + X -

[0226] Wherein R is a linear or branched, substituted or unsubstituted C 6-18 Alkyl or alkenyl moiety, R1 and R2 are independently selected from methyl or ethyl moieties, R3 is a hydroxyl, hydroxymethyl or hydroxyethyl moiety, and X is an anion providing electroneutrality, and preferred anions include: halide, preferably chloride; sulfate; and sulfonate.

[0227] Amphoteric and zwitterionic detersive surfactants: Suitable amphoteric or zwitterionic detersive surfactants include amine oxides and / or betaines. Preferred amine oxides are alkyl dimethyl amine oxides or alkyl amidopropyl dimethyl amine oxides, more preferably alkyl dimethyl amine oxides, and especially coconut dimethyl amine oxide. The amine oxide may have a linear or intermediate branched alkyl portion. Typical linear amine oxides include water-soluble amine oxides comprising one R1 C8-18 alkyl portion and two R2 and R3 portions selected from the group consisting of C1-3 alkyl and C1-3 hydroxyalkyl. Preferably, the amine oxide is characterized by the formula R1-N(R2)(R3)O, wherein R1 is a C8-18 alkyl, and R2 and R3 are selected from the group consisting of methyl, ethyl, propyl, isopropyl, 2-hydroxyethyl, 2-hydroxypropyl and 3-hydroxypropyl. Specifically, the linear amine oxide surfactant may include a linear C10-C18 alkyl dimethyl amine oxide and a linear C8-C12 alkoxy ethyl dihydroxy ethyl amine oxide.

[0228] Other suitable ionic surfactants include betaines, such as alkyl betaines, alkyl amido betaines, amidazolinium betaines, sultaines (INCI sultaines) and phosphobetaines.

[0229] Antimicrobial compounds

[0230] In embodiments, the soluble active agent may include an effective amount of a compound for reducing the number of live microorganisms in the air or on an inanimate surface. Antimicrobial compounds are effective for gram-negative or gram-positive bacteria or fungi that are usually present on indoor surfaces such as sofas, pillows, pet bedding and carpets that contact human skin or pets. Such microbial strains include Klebsiella pneumoniae, Staphylococcus aureus, Aspergillus niger, Klebsiella pneumoniae, Steptococcus pyogenes, Salmonella choleraesuis, Escherichia coli, Trichophyton mentagrophytes and Pseudomonas aeruginosa. Antimicrobial compounds are also able to effectively reduce the number of live viruses, such as H1-N1, rhinovirus, respiratory syncytial virus, polio virus type 1, rotavirus, influenza A virus, herpes simplex type 1 and 2, hepatitis A virus, and human coronavirus.

[0231] Antimicrobial compounds suitable for rheological solid compositions can be any organic material that does not cause damage to the appearance of the fabric (e.g., discoloration, coloration such as yellowing, bleaching). Water-soluble antimicrobial compounds include organic sulfur compounds, halogenated compounds, cyclic organic nitrogen compounds, low molecular weight aldehydes, quaternary compounds, dehydroacetic acid, phenyl and phenoxy compounds or mixtures thereof.

[0232] Quaternary compounds may be used. Examples of commercially available quaternary compounds suitable for use in the rheological solid composition are Barquat from Lonza Corporation; and 2250 was a didecyldimethylammonium chloride quaternary compound available from Lonza Corporation.

[0233] The antimicrobial compound may be present in an amount of about 500 ppm to about 7000 ppm, alternatively about 1000 ppm to about 5000 ppm, alternatively about 1000 ppm to about 3000 ppm, alternatively about 1400 ppm to about 2500 ppm by weight of the rheological solid composition.

[0234] preservative

[0235] In an embodiment, the soluble active agent may include a preservative. The preservative may be present in an amount sufficient to prevent spoilage or prevent the growth of inadvertently added microorganisms for a specific period of time, but not sufficient to contribute to the odor neutralization properties of the rheological solid composition. In other words, the preservative does not act as an antimicrobial compound to kill microorganisms on the surface on which the rheological solid composition is deposited, thereby eliminating odors produced by the microorganisms. Instead, it is used to prevent spoilage of the rheological solid composition to extend the shelf life of the rheological solid composition.

[0236] The preservative can be any organic preservative material that does not cause damage to the appearance of the fabric (e.g., discoloration, coloring, bleaching). Suitable water-soluble preservatives include organic sulfur compounds, halogenated compounds, cyclic organic nitrogen compounds, low molecular weight aldehydes, parabens, propylene glycol materials, isothiazolinones, quaternary compounds, benzoates, low molecular weight alcohols, dehydroacetic acid, phenyl and phenoxy compounds or mixtures thereof.

[0237] A non-limiting example of a commercially available water-soluble preservative includes a mixture of about 77% 5-chloro-2-methyl-4-isothiazolin-3-one and about 23% 2-methyl-4-isothiazolin-3-one sold by Rohm and Haas Co. under the trade name CG is a broad-spectrum preservative sold as a 1.5% aqueous solution; 5-bromo-5-nitro-1,3-dioxane, which is sold under the trade name Bronidox Available from Henkel; 2-bromo-2-nitropropane-1,3-diol, which is sold under the trade name Available from Inolex; 1,1'-hexamethylenebis(5-(p-chlorophenyl)biguanide) (commonly known as chlorhexidine) and its salts, such as those with acetic acid and digluconic acid; a 95:5 mixture of 1,3-bis(hydroxymethyl)-5,5-dimethyl-2,4-imidazolidinedione and 3-butyl-2-iodopropynylcarbamate, which is sold under the trade name Glydant Available from Lonza; N-[1,3-bis(hydroxymethyl)2,5-dioxo-4-imidazolidinyl]-N,N'-bis(hydroxy-methyl)urea, which is commonly known as diazolidinyl urea and sold under the trade name II was purchased from Sutton Laboratories, Inc.; N,N"-methylenebis{N'-[1-(hydroxymethyl)-2,5-dioxo-4-imidazolidinyl]urea}, which is commonly known as imidazolidinyl urea, for example, under the trade name Available from 3V-sigma under the trade name Unicide Purchased from Induchem under the trade name Ger-mall Available from Sutton Laboratories, Inc.; polymethoxybicyclic oxazolidine, which is sold under the trade name C was purchased from Hüls America; formaldehyde; glutaraldehyde; polyaminopropyl biguanide, which is sold under the trade name Cosmocil Available from ICI Americas, Inc., or under the trade name Available from Brooks, Inc; dehydroacetic acid; and benzisothiazolinone, which is sold under the trade name Koralone TM B-119 was purchased from Rohm and Hass Corporation; 1,2-benzisothiazoline-3-one; Acticide MBS.

[0238] Suitable levels of preservatives are from about 0.0001 wt % to about 0.5 wt %, alternatively from about 0.0002 wt % to about 0.2 wt %, alternatively from about 0.0003 wt % to about 0.1 wt %, based on the weight of the rheological solid composition.

[0239] Adjuvant

[0240] Adjuvants may be added to the rheological solid compositions herein for their known purposes. Such adjuvants include, but are not limited to, water-soluble metal salts, including zinc salts, copper salts, and mixtures thereof; antistatic agents; insect and moth repellents; colorants; antioxidants; aromatherapeutic agents, and mixtures thereof.

[0241] The composition of the present invention may also contain any additives commonly used in the field under study. For example, unencapsulated pigments, film formers, dispersants, antioxidants, essential oils, preservatives, fragrances, fat-soluble polymers dispersible in a medium, fillers, neutralizers, silicone elastomers, cosmetic and skin care oil-soluble active agents such as emollients, moisturizers, vitamins, anti-wrinkle agents, essential fatty acids, sunscreens, and mixtures thereof may be added.

[0242] Solvents

[0243] The composition may contain a solvent. Non-limiting examples of solvents may include ethanol, glycerol, propylene glycol, polyethylene glycol 400, polyethylene glycol 200, and mixtures thereof. In one example, the composition contains about 0.5% to about 15% solvent, in another example about 1.0% to about 10% solvent, and in another example about 1.0% to about 8.0% solvent, and in another example about 1% solvent to about 5% solvent.

[0244] Vitamins

[0245] As used herein, "xanthine compound" means one or more xanthines, their derivatives, and mixtures thereof. Xanthine compounds useful herein include, but are not limited to, caffeine, xanthine, 1-methylxanthine, theophylline, theobromine, their derivatives, and mixtures thereof. Among these compounds, caffeine is preferred in view of its solubility in the composition. The composition may contain by weight from about 0.05%, preferably from about 2.0%, more preferably from about 0.1%, still more preferably from about 1.0%, and to about 0.2%, preferably to about 1.0%, more preferably to about 0.3% of xanthine compounds.

[0246] As used herein, "vitamin B3 compound" refers to one or more compounds having the formula:

[0247]

[0248] Wherein R is -CONH2 (ie nicotinamide), -COOH (ie nicotinic acid) or -CH2OH (ie nicotinic alcohol); their derivatives; their mixtures; and salts of any of the foregoing substances.

[0249] Exemplary derivatives of the foregoing vitamin B3 compounds include nicotinic acid esters, including non-vasodilating nicotinic acid esters (e.g., tocopheryl nicotinate and myristyl nicotinate), nicotinyl amino acids, nicotinyl alcohol esters of carboxylic acids, nicotinic acid N-oxide, and nicotinamide N-oxide. The composition may contain from about 0.05%, preferably from about 2.0%, more preferably from about 0.1%, still more preferably from about 1.0%, and to about 0.1%, preferably to about 0.5%, more preferably to about 0.3% by weight of the vitamin B3 compound.

[0250] As used herein, the term "panthenol compound" is broad enough to include panthenol, one or more pantothenic acid derivatives, and mixtures thereof. Panthenol and its derivatives may include D-panthenol ([R]-2,4-dihydroxy-N-[3-hydroxypropyl]-3,3-dimethylbutyramide), DL-panthenol, pantothenic acid and its salts (preferably calcium salts), panthenol triacetate, royal jelly, pantethine, panthenylthioethylamine, panthenyl ethyl ether, pancreatic acid, pantothenic acid lactose, vitamin B complexes, or mixtures thereof. The composition may contain from about 0.01%, preferably from about 0.02%, more preferably from about 0.05%, and to about 3%, preferably to about 1%, more preferably to about 0.5% by weight of a panthenol compound.

[0251] Sodium chloride (and other sodium salts) are particularly useful additives to the aqueous phase to adjust the thermal stability of the composition, but must be added to the composition with particular care (Example 3). Without wishing to be bound by theory, sodium chloride is thought to "salt out" the crystallizer of the present invention, thereby reducing its solubility. This has the effect of increasing the thermal stability temperature of the rheological solid composition, as measured by the thermal stability test method. For example, the crystallizer of the optimal chain length can have a thermal stability temperature increased by up to 15°C after the addition of sodium chloride. This is particularly valuable because the addition of other ingredients to the aqueous phase in the absence of sodium chloride typically reduces the thermal stability temperature. Surprisingly, the addition of sodium chloride can cause adverse effects in the preparation of rheological solid compositions. In most preparation methods, sodium chloride is preferably added to the hot crystallizer aqueous phase before cooling to form a network. However, too much addition may result in "coagulation" of the crystallizer and an absolutely unpleasant composition. Sodium chloride can also be added after the network is formed to provide the beneficial effect of increasing the thermal stability temperature at a higher level without coagulation. Finally, while the thermal stability temperature increases with the addition of sodium chloride, the addition of other non-sodium salts can also change the fibrous nature of the crystals formed by the crystallizing agent to form flake or plate-like crystals that are not rheologically solid.

[0252] PEGC domain

[0253] Polyethylene glycol (PEG) material is the preferred carrier material of the non-porous solid soluble domain of the present invention.PEG material has relatively low cost usually, can be formed into many different shapes and sizes, dissolves well in water, and liquefies at elevated temperatures.PEG material has various molecular weights.In the consumer product composition of the present invention, the molecular weight of PEG carrier material is about 200 daltons to about 50,000 daltons, preferably about 500 daltons to about 20,000 daltons, preferably about 1,000 daltons to about 15,000 daltons, preferably about 1,500 daltons to about 12,000 daltons, alternatively about 6,000 daltons to about 10,000 daltons, and the combination of these data.Suitable PEG carrier material comprises that molecular weight is about 8,000 daltons of material, molecular weight is about 400 daltons of PEG material, molecular weight is about 20,000 daltons of PEG material, or the mixture of these materials. Suitable PEG carrier materials are commercially available from BASF under the trade name PLURIOL, such as PLURIOL E 8000.

[0254] In one embodiment, the PEGC domain contains less than about 30% by weight of pure fragrance; in another embodiment, the PEGC domain contains between 15% and 1% by weight of pure fragrance; in another embodiment, the PEGC domain contains between 12% and 2% by weight of pure fragrance; in another embodiment, the PEGC domain contains between 12% and 5% by weight of pure fragrance; in another embodiment, the PEGC domain contains between 10% and 2% by weight of pure fragrance, as exemplified by "% Freshener" in the Examples.

[0255] In one embodiment, the PEGC domain contains less than about 2 wt% of fragrance capsules; in another embodiment, the PEGC domain contains between 1.5 wt% and 0.1 wt% of fragrance capsules; in another embodiment, the PEGC domain contains between 1.25 wt% and 0.2 wt% of fragrance capsules; in another embodiment, the PEGC domain contains between 1.25 wt% and 0.5 wt% of fragrance capsules, as exemplified by "% Freshener" in the Examples.

[0256] Particles

[0257] The granular composition can be varied depending on the needs of the low water content composition.

[0258] As a non-limiting example, where the particle consists essentially of one domain. In one embodiment, the active agent is dispersed primarily in the particles consisting of SDC in the capsule; in another embodiment, the active agent is dispersed primarily in the particles consisting of SDC; in one embodiment, the active agent is dispersed primarily in the particles consisting of PEGC in the capsule; in another embodiment, the active agent is dispersed primarily in the particles consisting of PEGC; in one embodiment, the active agent includes the capsule and the active agent dispersed primarily in the particles consisting of SDC; in one embodiment, the active agent is the capsule and the active agent dispersed primarily in the particles consisting of PEGC.

[0259] As a non-limiting example, where the particle is composed of two or more domains. In these cases, the SDC is small and completely enclosed in the PEGC domain. In one embodiment, the active agent is a capsule dispersed primarily in the particle composed of the SDC domain, which is dispersed in the PEGC domain ( Figure 7 , Example 1); in another embodiment, the active agent is a capsule dispersed primarily in a particle consisting of an SDC domain, which is dispersed in a PEGC domain. In another embodiment, the active agent is primarily dispersed in a particle consisting of an SDC domain, which is dispersed in a PEGC domain containing an active agent capsule. Typical particles contain less than about 50% by weight of SDC domain; in another embodiment, between about 45% and 10% by weight of SDC domain; in another embodiment, between about 40% and 15% by weight of SDC domain; in another embodiment, between about 35% and 20% by weight of SDC domain.

[0260] As a non-limiting example, where the particle is composed of two or more domains. In these cases, the core of the particle is a single SDC domain, which is covered by and completely enclosed in a coating of PEGC domains. In one embodiment, the active agent is a capsule dispersed primarily in the particle composed of SDC domains, which are dispersed in the PEGC domains ( Figure 8 , Example 2); in another embodiment, the active agent is a capsule dispersed primarily in a particle consisting of an SDC domain, which is dispersed in a PEGC domain. In another embodiment, the active agent is primarily dispersed in a particle consisting of an SDC domain, which is dispersed in a PEGC domain containing an active agent capsule. Typical particles contain less than about 90% by weight of SDC domains; in another embodiment, between about 80% and 40% by weight of SDC domains; in another embodiment, between about 80% and 50% by weight of SDC domains; in another embodiment, between about 50% and 35% by weight of SDC domains.

[0261] As a non-limiting example, where the particle is composed of two or more domains. In these cases, the core of the particle is a PEGC domain with SDC domains interspersed therein. In one embodiment, the active agent is a capsule dispersed primarily in the particle composed of SDC domains, which are dispersed in the PEGC domains ( Fig. 9 , Example 3); in another embodiment, the active agent is a capsule dispersed primarily in particles consisting of SDC domains dispersed in PEGC domains containing the active agent. In another embodiment, the active agent is primarily dispersed in particles consisting of SDC domains dispersed in PEGC domains. Typical particles contain less than 25% by weight SDC domains; in another embodiment, between about 20% and 2% by weight SDC domains; in another embodiment, between about 15% and 5% by weight SDC domains.

[0262] As a non-limiting example, where the particle is composed of two or more domains. In these cases, one side of the particle contains a PEGC domain and the other side contains an SDC domain. In one embodiment, the active agent is a capsule dispersed primarily in the particle composed of an SDC domain, which is dispersed in the PEGC domain ( Fig.10 , Example 4); in another embodiment, the active agent is a capsule dispersed primarily in a particle consisting of an SDC domain, which is dispersed in a PEGC domain. In another embodiment, the active agent is primarily dispersed in a particle consisting of an SDC domain, which is dispersed in a PEGC domain containing an active agent capsule. Typical particles contain between about 75% and 25% by weight of SDC domains; in another embodiment, between 70% and 30% by weight of SDC domains; in another embodiment, between 60% and 40% by weight of SDC domains.

[0263] In an embodiment, the particles of the low water content composition have a certain shape, which may include hemispherical, plate-like, cubic, cashew-shaped, jelly bear-shaped, tubular and spherical. In another embodiment, the longest dimension of the particles is 3 cm. In another embodiment, the average weight of the particles is less than about 1,000 mg, between about 750 mg and 1 mg, and between about 500 mg and 5 mg.

[0264] Low water content composition

[0265] The low water content composition consists of one or more particles and contains at least one SDC domain and at least one PEGC domain (Example 5).

[0266] When summed over all particles, the proportion of SDC domains in the low water content composition can be between about 10 wt % and about 90 wt %, or between about 10 wt % and about 70 wt %, or between about 30 wt % and about 90 wt %, or between about 40 wt % and about 60 wt %.

[0267] When all particles are summed, the proportion of the PEGC domain in the low water content composition can be between about 10 wt % and about 90 wt %, or between about 10 wt % and about 70 wt %, or between about 30 wt % and about 90 wt %, or between about 40 wt % and about 60 wt %.

[0268] Consumer product compositions

[0269] In one embodiment, the consumer product is added directly to the washing machine drum at the beginning of the wash; in another embodiment, the consumer product is added to the fabric enhancer cup in the washing machine; in another embodiment, the consumer product is added at the beginning of the wash; in another embodiment, the consumer product is added during the wash.

[0270] In one embodiment, the consumer product is sold in paper packaging due to the hydration and temperature stability of the composition; in one embodiment, the consumer product is sold in unit dose packaging; in one embodiment, the consumer product is sold with particles of different colors; in one embodiment, the consumer product is sold in pouches; in one embodiment, the consumer product is sold with particles of different colors; in one embodiment, the consumer product is sold in a recyclable container.

[0271] Dissolution Test Method

[0272] All samples and procedures were kept at room temperature (25 ± 3°C) prior to testing and then placed in a desiccant chamber (0% RH) for 24 hours or until they reached constant weight.

[0273] All dissolution measurements were carried out at controlled temperature and constant stirring rate. Attached 600mL jacketed beaker (Cole-Palmer, product number UX-03773-30, or equivalent), water was circulated through the jacketed beaker using a water circulator (Fisherbrand Isotemp 4100, or equivalent) set to the desired temperature to cool to a certain temperature. The jacketed beaker was centered on the stirring element of a VWR multi-position stirrer (VWR North American, West Chester, Pa., USA catalog number 12621-046). 100mL deionized water (model 18MΩ, or equivalent) and a stirring bar (VWR, Spinbar, catalog number 58947-106, or equivalent) were added to a second 150mL beaker (VWR North American, West Chester, Pa., USA catalog number 58948-138, or equivalent). Place the second beaker into the jacketed beaker. Add enough Millipore water to the jacketed beaker to bring it above the water level in the second beaker, being very careful so that the water in the jacketed beaker does not mix with the water in the second beaker. The speed of the stir bar is set to 200 RPM, enough to create a gentle vortex. The temperature in the second beaker is set to reach 25°C or 37°C using water flow from a water circulator, the relevant temperatures are reported in the examples. Before performing the dissolution experiment, measure the temperature in the second beaker with a thermometer.

[0274] All samples were sealed in a desiccator prepared with fresh desiccant (VWR, Indicating Anhydrous Drierite, Stock No. 23001, or equivalent) until constant weight was reached. The mass of all tested samples was less than 15 mg.

[0275] Take out a single sample from the desiccator for a single dissolution test. After taking the sample out of the desiccator, weigh it within 1 minute and measure the initial mass (M I ). The sample is dripped into the second beaker under stirring. The sample is allowed to dissolve for 1 minute. At the end of this minute, the sample is carefully removed from the deionized water. The sample is placed in the desiccator again until a constant final mass is reached. The percentage mass loss of the sample in a single experiment is calculated as M L =100*(M I -M F ) / M I calculate.

[0276] Nine additional dissolution experiments were performed: first replacing 100 ml of water with fresh deionized water, adding new sample to the desiccator for each experiment, and then repeating the dissolution experiment described in the previous paragraph.

[0277] The average mass loss percentage of the test (M A ) was calculated based on the average mass loss percentage of these ten experiments, and the standard deviation of the average mass loss (SD A ) is the standard deviation of the average mass loss percentage of these ten experiments.

[0278] This method returns three values: 1) the average mass of the sample (M S ), 2) the temperature at which the sample dissolved (T), and 3) the average percent mass loss (M A If the method is not performed on a sample, the method returns "NM" for all values. Average mass loss percentage (M A ) and the average standard deviation (SD A ) is used to draw Figure 4A , Figure 4B and Figure 4C Dissolution curves used in this study.

[0279] Humidity test method

[0280] The humidity test method is used to determine the amount of water vapor adsorption that occurs when a composition is dried at 0% RH and various RH at 25°C. In this method, 10 mg to 60 mg of sample are weighed and the mass changes associated with conditioning with different environmental states are captured in a dynamic vapor sorption instrument. The resulting mass increase is expressed as a mass change per % of the mass of the dried sample recorded at 0% RH.

[0281] The method uses an SPSx vapor sorption analyzer with 1 μg resolution (ProUmid GmbH & Co. KG, Ulm, Germany), or an equivalent dynamic vapor sorption (DVS) instrument capable of controlling the relative humidity percentage (%RH) within ±3%, the temperature within ±2°C, and the mass measurement accuracy within ±0.001 mg.

[0282] 10 mg to 60 mg of the raw material or composition sample is evenly dispersed into a tared 1" diameter aluminum pan. The aluminum pan with the raw material or composition sample dispersed thereon is placed in a DVS instrument set to 25°C and 0% RH. At this set point, the mass is recorded approximately every 15 minutes to an accuracy of 0.001 mg or better. After the sample has been in the DVS at this environmental setting for at least 12 hours and a constant weight has been reached, the mass of the sample, md, is recorded to an accuracy of 0.01 mg or better. After this step is completed, the instrument is advanced in 10% RH increments until 90% RH. The sample is maintained in the DVS for at least 12 hours at each step until a constant weight has been reached. The mass of the sample, md, is recorded at each step. n , to an accuracy of 0.001mg or better.

[0283] For a particular sample, constant weight can be defined as the mass variation of successive weighings not exceeding 0.004%. For a particular sample, the mass variation per dry sample mass (% dm) is defined as

[0284]

[0285] % Mass change is reported in % per dried sample mass to the nearest 0.01%.

[0286] Humidity stability at 80% RH means a change at 80% RH of less than or equal to 5%; no humidity stability at 80% RH means a change at 80% RH of greater than 5%.

[0287] Thermal stability test method

[0288] All samples and procedures were maintained at room temperature (25 ± 3°C) prior to testing and at a relative humidity of 40% ± 10% for 24 hours prior to testing.

[0289] In the thermal stability test method, a 20 mg ± 10 mg sample of the sample composition is subjected to differential scanning calorimetry (DSC). A simple scan is performed between 25°C and 90°C, and the temperature at which the maximum peak is observed is reported as the stable temperature, accurate to the nearest °C.

[0290] The sample was loaded into the DSC pan. All measurements were performed in a high capacity stainless steel pan set (TA part number 900825.902). The pan, lid, and liner were weighed and tared on a Mettler Toledo MT5 analytical microbalance (or equivalent; Mettler Toledo, LLC., Columbus, OH). The sample was loaded into the pan according to the manufacturer's instructions with a target weight of 20 mg (+ / - 10 mg), taking care to ensure that the sample was in contact with the bottom of the pan. The pan was then sealed with a TA high capacity die set (TA part number 901608.905). The final assembly was measured to obtain the sample weight. The sample was loaded into a TA Q Series DSC (A Instruments, New Castle, DE) according to the manufacturing instructions. The DSC program used the following settings: 1) equilibrate at 25°C; 2) mark the end point of cycle 1; 3) heat up to 90.00°C at 1.00°C / min; 4) mark the end point of cycle 3; then 5) end the method; click Run.

[0291] Moisture Testing Methods

[0292] All samples and procedures were maintained at room temperature (25 ± 3°C) prior to testing and at a relative humidity of 40% ± 10% for 24 hours prior to testing.

[0293] The moisture test method is used to quantify the weight percentage of water in a composition. In this method, a Karl Fischer (KF) titration is performed on each of three similar samples of the sample composition. A volumetric KF titration apparatus is used and the titration is performed using a single component solvent system. The sample mass is 0.3 g ± 0.05 g and is allowed to dissolve in the titration vessel for 2.5 minutes prior to titration. The average (arithmetic mean) water content of the three replicates is recorded to the nearest 0.1 weight % of the sample composition.

[0294] In order to measure the water content of the sample, a Mettler Toledo V30S volumetric KF titrator was used for measurement. The instrument used Honeywell Fluka Hydraanal solvent (catalog number 34800-1L-US) to dissolve the sample, used Honeywell Fluka Hydranal titrant-5 (catalog number 34801-1L-US) to titrate the sample, and was equipped with three drying tubes filled with Honeywell Fluka Hydranal 3nm molecular sieves (catalog number 34241-250g) to maintain the efficacy of anhydrous materials.

[0295] The method used to measure the sample is of type "KF vol", ID "U8000", and title "KFVol2-comp 5", and has eight rows, each of which is a method function.

[0296] Row 1, "Title" has the following selected: "Type" is set to "Karl Fischer Volumetric Titration"; "Compatibility" is set to "V10S / V20S / V30S / T5 / T7 / T9"; "ID" is set to "U8000"; "Title" is set to "KFVol 2-comp 5"; "Initiator" is set to "Administrator"; "Date / Time" along with "Modified Time" and "Modified By" are defined by the following: when the method was created; "Protection" is set to "No"; "SOP" is set to "None".

[0297] In the second row, "Sample" has two options, "Sample" and "Concentration". When the "Sample" option is selected, the following fields are defined: "Number of IDs" is set to "1"; "ID 1" is set to "--"; "Entry Type" is selected as "Weight"; "Lower Limit" is set to "0.0g";

[0298] "Upper limit" is set to "5.0g"; "Density" is set to "1.0g / mL"; "Correction factor" is set to "1.0"; "Temperature" is set to "25.0℃"; "Auto start" is selected;

[0299] 'Entry' is set to 'After Addition'. When the 'Concentration' option is selected, the following fields are defined: 'Titrant' is selected as 'KF 2-comp 5'; 'Nominal Concentration' is set to '5mg / mL'; 'Standard' is selected as 'Water-Standard 10.0'; 'Entry Type' is selected as 'Weight'; 'Lower Limit' is set to '0.0g'; 'Upper Limit' is set to '2.0g'; 'Temperature' is set to '25.0℃'; 'Maximum Time' is set to '10s'; 'Auto Start' is selected; 'Entry' is selected as 'After Addition'; 'Lower Concentration Limit' is set to '4.5mg / mL'; 'Upper Concentration Limit' is set to '5.6mg / mL'.

[0300] Row 3, "Titration stand (KF stand)" has the following defined fields: "Type" is set to "KF stand"; "Titration stand" is selected as "KF stand"; "Drift source" is selected as "Online"; "Maximum starting drift" is set to "25.0 μg / min".

[0301] Row 4, "Mixing Time" has the following fields defined: "Duration" is set to "150s".

[0302] Row 5, "Titration (KF Vol)" [1] has six options, "Titrants", "Sensors", "Stirring", "Predispensing", "Control", and "Stop". When the "Titrants" option is selected, the following fields are defined: "Titrants" is selected as "KF2-comp 5"; "Nominal Concentration" is set to "5 mg / mL"; "Reagent Type" is set to "2-comp". When the "Sensors" option is selected, the following fields are defined: "Type" is set to "Polarization";

[0303] "Sensor" is selected as "DM143-SC"; "Unit" is set to "mV"; "Indication" is set to "Voltammetry"; "Ipol" is set to "24.0μA". When the "Stirring" option is selected, the following fields are defined: "Speed" is set to "50%". When the "Pre-dispensing" option is selected, the following fields are defined: "Mode" is selected as "None"; "Wait time" is set to "0s". When the "Control" option is selected, the following fields are defined: "Endpoint" is set to "100.00mV"; "Control band" is set to "400.00mV"; "Dosing rate (maximum)" is set to "3mL / min"; "Dosing rate (minimum)" is set to "100μL / min"; "Start" is selected as "Normal". When the "Termination" option is selected, the following fields are defined: "Type" is selected as "Drift Relative Stop"; "Drift" is set to "15.0μg / min"; "Vmax" is set to "15mL"; "Minimum Time" is set to "0s"; and "Maximum Time" is set to

[0304] Row 6, "Calculation" has the following fields defined: "Result Type" is selected as "Predefined"; "Result" is set to "Amount"; "Result Unit" is set to "%";

[0305] "Formula" is set to "R1=(VEQ*CONC-TIME*D…)"; "Constant C=" is set to "0.1"; "Decimal places" is set to 2; "Result limit" is not selected; "Record statistical values" is selected; no additional statistical functions are selected.

[0306] Row 7, "Record" has the following fields defined: "Summary" is selected as "Per Sample"; "Result" is selected as "No"; "Raw Result" is selected as "No"; "Measurement Table" is selected as "No"; "Sample Data" is selected as "No"; "Resource Data" is selected as "No"; "EV" is selected as "No"; "Et" is selected as "No";

[0307] “Vt” is selected as “No”; “H2O-t” is selected as “No”; “Drift-t” is selected as “No”; “H2O-t and Drift-t” is selected as “No”; “Vt and Drift-t” is selected as “No”; “Method” is selected as “No”; “Series data” is selected as “No”.

[0308] Row 8, End of Sample has the following fields defined: Select "Open Series".

[0309] After selecting the method and pressing the "Start" button, the following fields are defined: "Type" is set to "Method"; "Method ID" is set to "U8000"; "Number of Samples" is set to "1"; "ID 1" is set to "--"; and "Sample Size" is set to 0g. Press the "Start" option again. The instrument will measure the "Maximum Drift" and once steady state is reached, the user will be allowed to select "Add" sample, at which point the user will attach the three-hole adapter and remove the stopper, place the sample in the titration beaker, reattach the three-hole adapter and stopper, and then enter the mass of the sample (g) into the touch screen. The value reported will be the weight percentage of water in the sample. Repeat this measurement three times for each sample and report the average of these three measurements.

[0310] Fiber Test Methods

[0311] The Fiber Test Method is used to determine whether a solid soluble composition crystallizes under process conditions and contains fibrous crystals. A fiber is simply defined as a "filament, or a filament-like structure or object." A fiber has a long length in only one direction ( Figure 1A and Figure 1B This is different from other crystal forms, such as plates or flakes, which have long lengths in two or more directions ( Fig.11A and Fig. 11B Only solid soluble compositions in which the DCS is a fiber fall within the scope of the present invention. One skilled in the art will recognize the SDC domain from the PEGC domain in a solid soluble composition provided that the two domains are present in the same particle.

[0312] The sample measuring about 4 mm in diameter was mounted on a SEM sample shuttle and sample holder (Quorum Technologies, AL200077B and E7406) slit-precoated with a 1:1 mixture of Scigen Tissue Plus optimal cutting temperature (OCT) compound (Scigen 4586) and colloidal graphite (Agar Scientific G303E). The mounted sample was placed in a liquid nitrogen-slush bath and plunge-frozen. Next, the frozen sample was inserted into a Quorum PP3010T cryopreparation chamber (Quorum Technologies PP3010T) or equivalent and equilibrated to -120°C before freeze-fracture. Frozen fracture was performed by splitting the top of the glassy sample using an ice-cold built-in knife in the cryopreparation chamber. Additional sublimation was performed at -90°C for 5 minutes to remove residual ice on the sample surface. The sample was further cooled to -150 °C and sputter-coated with a layer of Pt, which was kept in a cryo-preparation chamber for 60 s to mitigate charging.

[0313] High-resolution imaging was performed in a Hitachi Ethos NX5000 FIB-SEM (Hitachi NX5000) or equivalent.

[0314] To determine the fiber morphology of the sample, imaging was performed at 20,000× magnification. At this magnification, single crystals of the crystallization agent can be observed. The magnification can be slightly adjusted to lower or higher values ​​until single crystals are observed. One skilled in the art can assess the longest dimension of a representative crystal in the image. If the longest dimension is about 10 times or more of the other orthogonal dimensions of the crystal, the crystals are considered fibers and are within the scope of the present invention.

[0315] Example

[0316] These examples provide non-limiting examples of low moisture content compositions comprising solid soluble composition (SDC) domains having a network microstructure formed from a dry sodium fatty acid carboxylate formulation, polyethylene glycol (PEGC) domains, and active agents such as freshness benefit agents dispersed into these domains that deliver exceptional freshness to fabrics.

[0317] The present compositions exhibit particles comprising SDC domains with a crystallizing agent which, when properly processed, forms a fibrous web that completely dissolves within a wash cycle. The present compositions also exhibit PEGC domains which, when used in combination with SDC domains, produce a unique low water content composition that is easy to process, provides unique aesthetic properties and enhanced freshness performance.

[0318] The freshness benefit agent takes the form of perfume capsules and / or pure perfume distributed in different domains. Example 1 shows a particle composed of two or more domains, where the SDC domain is smaller and completely enclosed in a single PEGC domain ( Figure 7 Example 2 demonstrates particles composed of two or more domains, wherein a single SDC domain is coated with a PEGC domain coating and is completely enclosed in the PEGC domain coating ( Figure 8 Example 3 shows particles composed of two or more domains, wherein the core of these particles is a PEGC domain and is interspersed with SDC domains ( Fig. 9 Example 4 shows particles composed of two or more domains, wherein one side of the particles contains a PEGC domain and the other side contains a SDC domain ( Fig.10). Example 5 presents a low moisture composition consisting of a physical mixture of two or more different types of particles and a novelty benefit agent, some of which are constructed as described in Examples 1 to 4. Example 6 presents a composition made from a specific blend of fatty acid materials that are neutralized with and blended with PEGC to produce a solid soluble composition and blended with fragrance capsules having different wall configurations.

[0319] The data in Tables 1 to 8 provide parameters about the particles in the following manner:

[0320] preparation SDC Domain - All weights listed in this section of the table correspond to the amount added to produce the solid soluble composition mixture (SDCM). "% Freshener (Dry)" is the weight percent of freshener remaining in the SDC after drying, assuming no remaining water, as determined by the "Moisture Test Method". "% Slow CA" is the weight percent of NaCl2 (slowly dissolving) in a mixture of NaCl2 with NaClO and NaC8 (fast dissolving).

[0321] All SDC domains were prepared in three fabrication steps to ensure the formation of a fiber mesh in the domains:

[0322] 1. mix - wherein the crystallization agent is completely dissolved in water to form the SDCM, optionally with the addition of an active agent;

[0323] 2. Forming - wherein the composition resulting from the mixing step is shaped according to the size and dimensions of the desired SDC by techniques including crystallization;

[0324] 3. dry - wherein the amount of water is reduced to ensure the desired properties, including dissolution, hydration and thermal stability, optionally with the addition of active agents.

[0325] Preparation of PEGC domain , all weights listed in this section of the table correspond to the amounts of PEG and freshener added to produce the PEGC. Any water added to this domain by including a fragrance capsule slurry is used when combining to form a low moisture composition. No Removed and stay to become part of the domain.

[0326] Low water content composition, all weights listed in this section of the table correspond to the amounts of SDC and PEGC combined to produce the low water content composition particles. For clarity, the percentages of the components in the low water content composition are provided as follows: "% CA", which is equal to the crystallization agent from SDC in the final low water content composition; "% flavor capsules", which is equal to the flavor capsules in the final low water content composition; "% flavor", which is equal to the pure flavor in the low water content composition; "% PEG", which is equal to the PEG in the low water content composition; "% water", which is equal to the water in the low water content composition, including the water not removed from the PEGC. Finally, "Average Mass" = the average mass of the particles produced from the low water content composition as described in each example.

[0327] The data in Tables 9-10 provide contemplated particles consisting solely of SDC domains with varying blends of crystalline agents and freshness benefit agents and PEGC domains with varying molecular weights of PEG and freshness benefit agents.

[0328] The data in Tables 11 to 12 provide a contemplated low-water composition comprising a physical mixture of particles having an SDC domain, a PEGC domain, and a freshness benefit agent. The amount of "perfume capsules in the wash liquor" is the dose of perfume capsules in the wash liquor that delivers the desired dry fabric feel benefit to the consumer. The amount of "pure perfume in the wash liquor" is the amount of pure perfume in the wash liquor that delivers the desired wet fabric feel benefit to the consumer. The @ symbol shown with the particles represents the mass of the particles in the low-water composition. The "composition dose" is the sum of all particles in the low-water composition and the amount added by the consumer to the wash liquor.

[0329] The data in Table 13 provide contemplated low moisture compositions comprising SDC domains prepared from a mixture of C8, C10, and C12 chain length fatty acids that are neutralized to produce SDC domains that are then combined with PEGC domains and with flavor capsules having different wall configurations.

[0330] Material

[0331] (1) Water: Millipore, Burlington, MA (18 m-ohm resistance)

[0332] (2) Sodium octanoate (NaC8): TCI Chemicals, catalog number 00034

[0333] (3) Sodium caprate (NaClO): TCI Chemicals, catalog number D0024

[0334] (4) Sodium laurate (sodium dodecanoate, NaCl2): TCI Chemicals, catalog number L0016

[0335] (5) Fragrance capsule slurry: Encapsys, Encapsulated Fragrance #1, Melamine Formaldehyde Wall Chemistry, (31% active)

[0336] (6) Fragrance capsule slurry: Encapsys, Encapsulated Fragrance #2, Urea wall chemistry, (21% active)

[0337] (7) PEG-6,000 g mol -1 , Alfa Aesar, product code A17541.30.

[0338] (8) PEG-8,000 g mol -1 , Alpha Aesar, product code 43443.

[0339] (9) PEG-9,000 g mol -1 , Dow Chemical, product code C4633240.

[0340] (10) PEG-10,000 g mol -1 , Alfa Aesar, product code B21955.30.

[0341] (11) Pure spices: International Flavors and Fragrances, Pure Spice Oil #1

[0342] (12) Fatty acid blend: C810L, Procter & Gamble Chemicals, sample code: SR26399

[0343] (13) Lauric acid: Peter Cremer, catalog number FA-1299 Lauric acid

[0344] (14) Sodium hydroxide (50 wt% solution): Fisher Scientific, catalog number SS254-4

[0345] (15) Fragrance capsule slurry: Encapsys, encapsulated fragrance #3 polyacrylate wall chemistry, 21 wt% active ingredient

[0346] (16) Fragrance capsule slurry: Encapsys, Encapsulated Fragrance #4, High Core to Wall Ratio, Polyacrylate Wall Chemistry, Encapsulated Fragrance #5, Polyurea Wall Chemistry, 32 wt% Active Ingredients

[0347] (17) Fragrance capsule slurry: Encapsulated fragrance #6, silica-based wall chemistry, 6.2 wt% active ingredient

[0348] Example 1

[0349] Example 1 demonstrates particles composed of two or more domains, wherein an SDC domain is completely enclosed within a single PEGC domain ( Figure 7 ).

[0350] This embodiment demonstrates the existence of compositions that can use different domains in a single particle to adjust the amount and distribution of different freshness benefit agents. In this non-limiting embodiment, the SDC domain is dispersed in the continuous domain of PEGC. This provides several advantages. First, the SDC domain provides an opportunity to increase the amount of flavor capsules in the particle (e.g., about 18% by weight) relative to a single PEGC domain (e.g., about 1.2% by weight). Second, these particles maintain a "smooth" appearance due to PEGC to enhance the aesthetics of the particles. Third, such compositions provide advantages for manufacturing, wherein the flow properties of the "molten" composition are similar to the flow properties of the full PEG composition, thereby providing the potential for preparing these composite compositions on existing commercial equipment. Samples AA to AI are non-limiting examples of the composition and weight ratio of different domains that may be present in the resulting particles, which can be used as low water content compositions.

[0351] preparation SDC Domain

[0352] Mixing - Place a 250 ml stainless steel beaker (Thermo Fischer Scientific, Waltham, MA.) on a hot plate (VWR, Radnor, PA, 7×7 CER hot plate, catalog number NO97042-690). Add water (Milli-Q Academic) and crystallization agent to the beaker. Place a temperature probe in the composition. Assemble a mixing apparatus including an overhead mixer (IKA Works Inc, Wilmington, NC, model RW20 DMZ) and a three-blade impeller design and place the impeller in the preparation. Set the heater to 80° C., set the impeller to rotate at 250 rpm, and then heat the composition to 80° C., or until all the crystallization agent is dissolved and the composition is clear. The preparation is then poured into a Max 100 Mid cup (Speed ​​Mixer), covered, and allowed to cool to 25° C. The preparation was spun in a Speedmixer (Flack Tek. Inc, Landrum, SC, Model DAC 150.1FVZ-K) at 3000 rpm for 3 minutes to add the fresh feel benefit agents as indicated in the table.

[0353] Forming - The preparation was poured onto aluminum foil to a uniform thickness of about 1 mm. The preparation was then placed in a refrigerator (VWR Door Solid Lock F refrigerator, 115V, 76300-508, or equivalent) equilibrated to 4°C for 8 hours to allow the crystallization agent to crystallize.

[0354] Drying - Place the preparation in a convection oven (Yamato, DKN400 or equivalent) set at 25°C for an additional 8 hours with a steady stream of air to dry the composition. Confirm that the final SDC has less than 10% moisture by the "Moisture Test Method". The domains are in the shape of the molds, or the flat plate is broken into coarse pieces of approximately 1 mm x 1 mm in size.

[0355] preparation PEGC domain

[0356] Separately, a 250 ml stainless steel beaker (Thermo Fischer Scientific, Waltham, MA.) was placed on a hot plate (VWR, Radnor, PA, 7×7 CER hot plate, catalog number NO97042-690). PEG (materials 8-11) was added to the beaker. A mixing apparatus including an overhead mixer (IKA Works Inc, Wilmington, NC, model RW20 DMZ) and a three-blade impeller design was assembled and the impeller was placed in the preparation. A temperature probe was also placed in the preparation. The impeller was set to rotate at 250 rpm. The preparation was heated to 100° C. until the PEG was completely melted. The preparation was placed in a Speedmixer high-speed mixer (Flack Tek. Inc, Landrum, SC, model DAC 150.1FVZ-K) and rotated at a rate of 3000 rpm for 3 minutes to add a fresh feeling benefit agent as indicated in the table. This preparation is used to prepare low water content compositions within 5 minutes of reaching the final temperature.

[0357] Preparation of low water content compositions

[0358] The 60 ml Speed ​​Mixer cup and lid were weighed. The lid was removed and the SDC domains were added to the cup. The cup was resealed with the lid and reweighed, and the mass of the SDC domains in the preparation was the weight difference.

[0359] Weigh a second 60 ml Speed ​​Mixer cup and lid. Remove lid and add freshness benefit agent to cup. Reseal cup with lid and re-weigh, where the mass of freshness benefit agent in preparation is the weight difference. Remove lid from cup again.

[0360] Within 30 seconds, PEGC was added to the cup, the lid was replaced, and the entire preparation was reweighed, where the mass of PEGC in the preparation was the weight difference. The cup was placed in a Speedmixer, started, and the preparation was mixed at 3,000 RPM for 1 minute. After mixing, within 30 seconds (and before crystallization), the preparation was transferred to a polymer mold patterned with 5 mm diameter hemispheres. The preparation was allowed to cool at 25°C for at least 30 minutes. The structure of the particles in the low water content composition is shown in Figure 7 Shown in.

[0361] Table 1

[0362]

[0363] Preparation SDC

[0364]

[0365] Preparation PEGC

[0366]

[0367]

[0368] Low water content composition

[0369]

[0370] Table 2

[0371]

[0372] Preparation SDC

[0373]

[0374] Preparation PEGC

[0375]

[0376]

[0377] Low water content composition

[0378]

[0379] Table 3

[0380]

[0381] Preparation SDC

[0382]

[0383] Preparation PEGC

[0384]

[0385]

[0386] Low water content composition

[0387]

[0388] Example 2

[0389] Example 2 demonstrates particles composed of two or more domains, wherein a single SDC domain is coated with a PEGC domain coating and is completely enclosed in the PEGC domain coating ( Figure 8 ).

[0390] This embodiment shows a composition in which particles having an SDC domain core and a PEGC coating are included. In this non-limiting embodiment, a single SDC domain is enclosed in a continuous PEGC domain. This has several advantages. These particles provide an opportunity to increase the amount of fragrance capsules in the SDC domain (e.g., up to about 18% by weight) relative to the amount of fragrance capsules in the SDC domain (e.g., only up to about 1.3% by weight). These particles are increased to about 10 times in terms of the capacity of the freshness benefit agent. The density of the SDC domain is also reduced by about 50% to 70%, making the particles (and the resulting low-water content composition) more suitable for different commercial approaches (such as e-commerce approaches), the carrier required for unit freshness is less and more sustainable, and it is more sustainable to replace petroleum-based PEG with natural crystallizers. In addition, the use of a PEGC coating allows the particles to maintain the "smooth" or shiny appearance of the PEGC domain, which is valued by many consumers. Samples BA to BI are non-limiting examples of the composition and weight ratio of different domains that may be present in the resulting particles.

[0391] Preparation of SDC domain

[0392] Mixing - Place a 250 ml stainless steel beaker (Thermo Fischer Scientific, Waltham, MA.) on a hot plate (VWR, Radnor, PA, 7×7 CER hot plate, catalog number NO97042-690). Add water (Milli-Q Academic) and crystallization agent to the beaker. Place a temperature probe in the composition. Assemble a mixing apparatus including an overhead mixer (IKA Works Inc, Wilmington, NC, model RW20 DMZ) and a three-blade impeller design and place the impeller in the preparation. Set the heater to 80° C., set the impeller to rotate at 250 rpm, and then heat the composition to 80° C., or until all the crystallization agent is dissolved and the composition is clear. The preparation is then poured into a Max 100 Mid cup (Speed ​​Mixer), covered, and allowed to cool to 25° C. The preparation was spun in a Speedmixer (Flack Tek. Inc, Landrum, SC, Model DAC 150.1FVZ-K) at 3000 rpm for 3 minutes to add the fresh feel benefit agents as indicated in the table.

[0393] Forming - The preparation was transferred to a polymer mold patterned with a 5 mm diameter hemisphere. The preparation was then placed in a refrigerator equilibrated to 4°C (VWR Door Solid Lock F refrigerator, 115V, 76300-508, or equivalent) for 8 hours to allow the crystallization agent to crystallize.

[0394] Drying - Place the preparation in a convection oven (Yamato, DKN400 or equivalent) set at 25°C for an additional 8 hours with a steady stream of air to dry the composition. Confirm that the moisture of the final SDC is less than 10% by the "Moisture Test Method".

[0395] Preparation of PEGC domain

[0396] Separately, a 250 ml stainless steel beaker (Thermo Fischer Scientific, Waltham, MA.) was placed on a hot plate (VWR, Radnor, PA, 7×7 CER hot plate, catalog number NO97042-690). PEG (materials 8-11) was added to the beaker. A mixing apparatus including an overhead mixer (IKA Works Inc, Wilmington, NC, model RW20 DMZ) and a three-blade impeller design was assembled and the impeller was placed in the preparation. A temperature probe was also placed in the preparation. The impeller was set to rotate at 250 rpm. The preparation was heated to 100° C. until the PEG was completely melted. The preparation was placed in a Speedmixer high-speed mixer (Flack Tek. Inc, Landrum, SC, model DAC 150.1FVZ-K) and rotated at a rate of 3000 rpm for 3 minutes to add a fresh feeling benefit agent as indicated in the table. This preparation is used to prepare low water content compositions within 5 minutes of reaching the final temperature.

[0397] Preparation of low water content compositions

[0398] Measure the weight of the weighing boat. Place the SDC in the weighing boat, wherein the weight of the SDC is determined by the difference in mass. Immerse the SDC in the PEGC melt. Wipe off excess PEGC from the surface of the SDC. Place the preparation in a weighing boat. Allow the preparation to cool at 25°C for at least 30 minutes. Measure the weight of the weighing boat, wherein the weight of the fragrance is determined by the difference in weight. A diagram of the structure of the particles in the low water content composition is shown in Figure 8 Shown in.

[0399] Table 4

[0400]

[0401] Preparation SDC

[0402]

[0403] Preparation PEGC

[0404]

[0405] Low water content composition

[0406]

[0407]

[0408] Table 5

[0409]

[0410] Preparation SDC

[0411]

[0412] Preparation PEGC

[0413]

[0414] Low water content composition

[0415]

[0416]

[0417] Table 6

[0418]

[0419] Preparation SDC

[0420]

[0421] Preparation PEGC

[0422]

[0423] Low water content composition

[0424]

[0425] Example 3

[0426] Example 3 demonstrates particles composed of two or more domains, wherein the core of these particles is a PEGC domain interspersed with SDC domains ( Fig. 9 ).

[0427] Such particles provide the opportunity that each domain has dissolution characteristics independently for particles with a large number of PEGC domains and SDC domains, for example. In non-limiting samples CA and CB, the flavor capsules are placed in the SDC domains and released into the washing cycle at a rate consistent with the composition of the crystallization agent blend, and the pure flavors are placed in the PEGC domains and released into the washing cycle at a rate consistent with the molecular weight of PEG. Compared with the particles described in, for example, Example 1, the solubility percentage determined by the "dissolution test method" is now independent of different domains. In addition, this form is aesthetically advantageous for consumers because the attached domains send signals that prompt different functions in the particles. In addition, this form is easy to prepare commercially-for example, warm PEGC domains are passed through "sporadic" SDC domain particles, which can adhere to the domain surface.

[0428] Preparation of SDC domain

[0429] Mixing - Place a 250 ml stainless steel beaker (Thermo Fischer Scientific, Waltham, MA.) on a hot plate (VWR, Radnor, PA, 7×7 CER hot plate, catalog number NO97042-690). Add water (Milli-Q Academic) and crystallization agent to the beaker. Place a temperature probe in the composition. Assemble a mixing apparatus including an overhead mixer (IKA Works Inc, Wilmington, NC, model RW20 DMZ) and a three-blade impeller design and place the impeller in the preparation. Set the heater to 80° C., set the impeller to rotate at 250 rpm, and then heat the composition to 80° C., or until all the crystallization agent is dissolved and the composition is clear. The preparation is then poured into a Max 100 Mid cup (Speed ​​Mixer), covered, and allowed to cool to 25° C. The preparation was spun in a Speedmixer (Flack Tek. Inc, Landrum, SC, Model DAC 150.1FVZ-K) at 3000 rpm for 3 minutes to add the fresh feel benefit agents as indicated in the table.

[0430] Forming - The preparation was poured onto aluminum foil to a uniform thickness of about 1 mm. The preparation was then placed in a refrigerator (VWR Door Solid Lock F refrigerator, 115V, 76300-508, or equivalent) equilibrated to 4°C for 8 hours to allow the crystallization agent to crystallize.

[0431] Drying - Place the preparation in a convection oven (Yamato, DKN400 or equivalent) set at 25°C for an additional 8 hours with a steady stream of air to dry the composition. Confirm that the final SDC has less than 10% moisture by the "Moisture Test Method". Break the plaque into coarse pieces of approximately 1 mm x 1 mm in size.

[0432] Preparation of PEGC domain

[0433] Separately, a 250 ml stainless steel beaker (Thermo Fischer Scientific, Waltham, MA.) was placed on a hot plate (VWR, Radnor, PA, 7×7 CER hot plate, catalog number NO97042-690). PEG (materials 8-11) was added to the beaker. A mixing apparatus including an overhead mixer (IKA Works Inc, Wilmington, NC, model RW20 DMZ) and a three-blade impeller design was assembled and the impeller was placed in the preparation. A temperature probe was also placed in the preparation. The impeller was set to rotate at 250 rpm. The preparation was heated to 100° C. until the PEG was completely melted. The preparation was placed in a Speedmixer high-speed mixer (Flack Tek. Inc, Landrum, SC, model DAC 150.1FVZ-K) and rotated at a rate of 3000 rpm for 3 minutes to add a fresh feeling benefit agent as indicated in the table. This preparation is used to prepare low water content compositions within 5 minutes of reaching the final temperature.

[0434] Preparation of low water content compositions

[0435] A small amount of PEGC was placed in a weighing boat and weighed. Before significant crystallization (within 30 seconds), a small amount of SDC was lightly sprinkled on the PEGC. Small-sized SDC domains adhered to the surface of the PEGC domains as crystalline material. The preparation was allowed to cool at 25°C for at least 30 minutes. The resulting particles were removed from the mold and reweighed to determine the relevant amount of SDC. The structure of the particles in this low water content composition is shown in Fig. 9 Shown in.

[0436] Table 7

[0437]

[0438] Preparation SDC

[0439]

[0440] Preparation PEGC

[0441]

[0442] Low water content composition

[0443]

[0444] Example 4

[0445] Example 4 demonstrates particles composed of two or more domains, wherein the particles contain a PEGC domain on one side and an SDC domain on the other side ( Fig.10 ).

[0446] Such particles also provide, for example, particles with a large number of PEGC domains and SDC domains, with the opportunity for each domain to have independent dissolution characteristics. In the non-limiting examples of samples DA and DB, the flavor capsules are placed in the SDC domains and released into the wash cycle at a rate consistent with the composition of the crystallization agent blend, and the pure flavor is placed in the PEGC domains and released into the wash cycle at a rate consistent with the molecular weight of PEG. Compared to the particles described in, for example, Example 1, the solubility percentage determined by the "Dissolution Test Method" is now independent of the different domains. In addition, relative to Example 3, this format has no restrictions on the absolute amount of SDC domains and PEGC domains in the particles.

[0447] Preparation of SDC domain

[0448] Mixing - Place a 250 ml stainless steel beaker (Thermo Fischer Scientific, Waltham, MA.) on a hot plate (VWR, Radnor, PA, 7×7 CER hot plate, catalog number NO97042-690). Add water (Milli-Q Academic) and crystallization agent to the beaker. Place a temperature probe in the composition. Assemble a mixing apparatus including an overhead mixer (IKA Works Inc, Wilmington, NC, model RW20 DMZ) and a three-blade impeller design and place the impeller in the preparation. Set the heater to 80° C., set the impeller to rotate at 250 rpm, and then heat the composition to 80° C., or until all the crystallization agent is dissolved and the composition is clear. The preparation is then poured into a Max 100 Mid cup (Speed ​​Mixer), covered, and allowed to cool to 25° C. The preparation was spun in a Speedmixer (Flack Tek. Inc, Landrum, SC, Model DAC 150.1FVZ-K) at 3000 rpm for 3 minutes to add the fresh feel benefit agents as indicated in the table.

[0449] Forming - The preparation was transferred to a polymer mold patterned with a 5 mm diameter hemisphere. The preparation was then placed in a refrigerator equilibrated to 4°C (VWR Door Solid Lock F refrigerator, 115V, 76300-508, or equivalent) for 8 hours to allow the crystallization agent to crystallize.

[0450] Drying - Place the preparation in a convection oven (Yamato, DKN400 or equivalent) set at 25°C for an additional 8 hours with a steady stream of air to dry the composition. Remove the preparation from the mold when it is completely dry. Confirm that the final SDC has less than 10% moisture by the "Moisture Test Method".

[0451] Preparation of PEGC domain

[0452] Separately, a 250 ml stainless steel beaker (Thermo Fischer Scientific, Waltham, MA.) was placed on a hot plate (VWR, Radnor, PA, 7×7 CER hot plate, catalog number NO97042-690). PEG (materials 8-11) was added to the beaker. A mixing apparatus including an overhead mixer (IKA Works Inc, Wilmington, NC, model RW20 DMZ) and a three-blade impeller design was assembled and the impeller was placed in the preparation. A temperature probe was also placed in the preparation. The impeller was set to rotate at 250 rpm. The preparation was heated to 100° C. until the PEG was completely melted. The preparation was placed in a Speedmixer high-speed mixer (Flack Tek. Inc, Landrum, SC, model DAC 150.1FVZ-K) and rotated at a rate of 3000 rpm for 3 minutes to add a fresh feeling benefit agent as indicated in the table. This preparation was used to prepare low water content compositions within 5 minutes of reaching the final temperature.The preparation was transferred to a polymer mold patterned with a 5 mm diameter hemisphere.

[0453] Preparation of low water content compositions

[0454] Within 30 seconds of placing the preparation in the mold, the SDC domains were placed on the liquid PEGC so that the flat side of the SDC was placed on the flat side of the PEGC. The preparation was allowed to cool at 25°C for at least 30 minutes. After the low water content composition was completely cooled, it was removed from the mold. The two domains attached and the resulting particles were spherical, as shown in FIG. Fig.10 As displayed.

[0455] Table 8

[0456]

[0457] Preparation SDC

[0458]

[0459] Preparation PEGC

[0460]

[0461]

[0462] Low water content composition

[0463]

[0464] Example 5

[0465] Example 5 demonstrates a low moisture composition consisting of two or more different particles, wherein these particles may contain a combination of SDC domains and PEGC domains as described in the previous example, or may contain only a single SDC domain and PEGC domain with a freshness benefit agent. These non-limiting examples are described later; however, it should be understood that physical blends of such particles to produce low moisture compositions may also include the aforementioned blends.

[0466] Granular composition sample EA-sample EH (Table 9 and Table 10) represents an active granular composition containing a single SDC domain or PEGC domain. Sample EI-sample EQ (Table 11 and Table 12) represents a low-water composition of the present invention consisting of a granular composition. The type and quantity of particles in the low-water composition are expressed as the "dose of the composition", or the typical amount used by consumers in a single wash. When determining the dosage, many considerations are important, including the amount of "spice capsules in the washing liquid" and the amount of "pure spices in the washing liquid" added by the dosage; however, other factors (such as the selection of the composition of the SDC domain or PEGC domain) are also important for delivering the degree of freshness benefits. For example, consumers may prefer an extra-long-lasting freshness on dry fabrics, which may require the addition of about 5 grams to 10 grams of spice capsule dosage in the washing liquid, or alternatively, consumers may prefer a freshness bursting only at the initial friction, which may require the addition of about 0.5 grams to 2 grams of spice capsule dosage in the washing liquid. For example, consumers may prefer a "flash" of freshness when wet fabrics are removed from the washing liquid, which may require about 5 grams to 10 grams of pure spices, or consumers may prefer a subtle, pleasant freshness aftertaste when wet fabrics are removed from the washing liquid, which may only require the addition of about 1 gram to 2 grams of pure spices in the washing liquid. These freshness characteristics are further affected by the dissolution rate of those domains containing freshness benefit agents. Finally, the selection of particles constituting low-water content compositions is also affected by commercial considerations. It is usually more commercially feasible to produce two types of particles and physically mix them in different proportions so that the composition can meet all consumer preferences, rather than using a special method for each consumer. This is generally referred to as "late product differentiation". Some consumers may prefer a dosage containing about 50 grams to 100 grams of bulk compositions, while some e-commerce consumers or consumers who focus on sustainability may prefer a more concentrated and compact dosage of about 10 grams to 20 grams. Finally, these embodiments provide a series of freshness performances and business opportunities.

[0467] Table 9

[0468]

[0469] SDC Domain

[0470]

[0471] PEGC domain

[0472]

[0473]

[0474] *Prepared from fragrance capsule slurry materials 5 and 6.

[0475] Table 10

[0476]

[0477] SDC Domain

[0478]

[0479] PEGC domain

[0480]

[0481] *Prepared from fragrance capsule slurry materials 5 and 6.

[0482] Table 11

[0483]

[0484] Preparation of low water content compositions

[0485]

[0486] Table 12

[0487]

[0488] Preparation of low water content compositions

[0489]

[0490] Example 6 Example 6 presents compositions prepared from a specific blend of fatty acid materials that are neutralized into an SDC composition and blended with a PEGC composition to produce a solid soluble composition wherein the SDC domains (e.g., Figure 4A , Figure 4B and Figure 4C ) and PEGC domains have different dissolution rate profiles, allowing for different ranking of actives within each domain at specific times in the wash cycle. The dissolution rate of SDC is affected by the percentage of slow crystallizer (% Slow CA), with those with higher percentage levels (e.g., sample EU) dissolving more slowly than those with lower percentage levels (e.g., sample ER). The absolute dissolution rates at different temperatures were determined by the "Dissolution Test Method". The dissolution rate of PEGC is affected by the molecular weight of PEG, such that sample ER (e.g., PEG 10,000) dissolves more slowly than sample ES (e.g., PEG 8,000), which in turn dissolves more slowly than sample ET and sample EU (e.g., PEG 6,000). The absolute dissolution rates at different temperatures were determined by the "Dissolution Test Method".

[0491] Preparation of SDC domain

[0492] mix - Place a 250 ml stainless steel beaker (Thermo Fischer Scientific, Waltham, MA.) on a hot plate (VWR, Radnor, PA, 7×7 CER hot plate, catalog number NO97042-690). Add water (Milli-Q Academic) and crystallization agent to the beaker. Place a temperature probe in the composition. Assemble a mixing apparatus including an overhead mixer (IKA Works Inc, Wilmington, NC, model RW20 DMZ) and a three-blade impeller design and place the impeller in the preparation. Set the heater to 80° C., set the impeller to rotate at 250 rpm, and then heat the composition to 80° C., or until all the crystallization agent is dissolved and the composition is clear.

[0493] Forming - The preparation was then poured into a Max 100 Mid cup (Speed ​​Mixer), covered with a lid, and allowed to cool to 25°C. The preparation was placed in a Speedmixer high-speed mixer (Flack Tek. Inc, Landrum, SC, model DAC150.1FVZ-K) and rotated at a rate of 3000 rpm for 3 minutes to add a fresh feeling benefit agent as indicated in the table. In one non-limiting embodiment, the preparation is transferred to a polymer mold patterned with a 5 mm diameter hemisphere. In another non-limiting embodiment, the preparation is sprayed through an orifice to produce small droplets. The size and shape of the DSC domain are formed to meet the requirements of the final structure of the final low water content composition (e.g., Figure 7 , Figure 8 , Fig. 9 and Fig.10 The preparation is then placed in a refrigerator (VWR Door Solid Lock F refrigerator, 115V, 76300-508, or equivalent) equilibrated to 4°C for 8 hours to allow the crystallization agent to crystallize.

[0494] Drying - Place the preparation in a convection oven (Yamato, DKN400 or equivalent) set at 25°C for an additional 8 hours with a steady stream of air to dry the composition. Remove the preparation from the mold when it is completely dry. Confirm that the final SDC has less than 10% moisture by the "Moisture Test Method".

[0495] Preparation of PEGC domain

[0496] Separately, a 250 ml stainless steel beaker (Thermo Fischer Scientific, Waltham, MA.) was placed on a hot plate (VWR, Radnor, PA, 7×7 CER hot plate, catalog number NO97042-690). PEG (materials 8-11) was added to the beaker. A mixing apparatus including an overhead mixer (IKA Works Inc, Wilmington, NC, model RW20 DMZ) and a three-blade impeller design was assembled and the impeller was placed in the preparation. A temperature probe was also placed in the preparation. The impeller was set to rotate at 250 rpm. The preparation was heated to 100° C. until the PEG was completely melted. The preparation was placed in a Speedmixer high-speed mixer (Flack Tek. Inc, Landrum, SC, model DAC 150.1FVZ-K) and rotated at a rate of 3000 rpm for 3 minutes to add a fresh feeling benefit agent as indicated in the table. In one non-limiting example, the preparation is used to prepare a low water content composition within 5 minutes after reaching the final temperature. In one non-limiting embodiment, the preparation is transferred to a polymer mold patterned with a 5 mm diameter hemisphere. The size and shape of the DSC domain are formed to meet the requirements of the final structure of the final low water content composition (e.g., Figure 7 , Figure 8 , Fig. 9 and Fig.10 ).

[0497] Preparation of low water content compositions

[0498] The sample ER (5 mg)-SDC composition was sprayed onto the plate in small droplets, crystallized, and then dried. PEGC was sprayed onto the plate and allowed to crystallize. The two plates were combined to produce low water content composition particles (e.g., Fig.10 ). The sample ES (5 mg)-SDC composition was sprayed onto a plate in small droplets, crystallized, and then dried. PEGC was sprayed onto the surface of the SDC composition to allow it to crystallize. The low-water composition was a coated particle (e.g., Figure 8 ). The sample ET (500 mg)-PEGC composition was placed on a plate as a large droplet, crystallized and then dried. SDC was sprayed to produce fine particles, which attached to the surface of the large droplet. The low-water composition was a sugar-gum-droplet-like particle (e.g., Fig. 9 ). Sample EU (500 mg)-SDC composition was spray dried small particles. Small SDC particles were added to the PEGC melt and large droplets were placed on a flat surface to allow crystallization. The low water content composition encapsulated the SDC (e.g. Figure 7 ).

[0499] Without limitation, the final low moisture composition for laundry treatment may contain particles including one of the combinations of particles described in Sample ER, Sample ES, Sample ET and Sample EU.

[0500] Table 13

[0501]

[0502] Preparation SDC

[0503] 1) Water 445g 447g 522g 231g 12)C8C10L 114g 91g 91g 66g 13) Lauric Acid 117g 141g 141g 158g 14) NaOH 105g 103g 103g 97g (15) Spice capsules 219g - - - (16) Spice capsules - 219g - - (17) Spice capsules - - 144g - (18) Spice capsules - - - 448g % Slow CA 50.0% 60% 60% 70%

[0504] Preparation PEGC

[0505] 7) PEG 6,000 - - 693g 90g 8) PEG 8,000 - 393g - - 9) PEG 9,000 - - - - 10) PEG 10,000 103g - - - 11) Spices 40g 40g 40g 20g

[0506] Low water content composition

[0507]

[0508] The dimensions and values ​​disclosed herein should not be understood as being strictly limited to the exact numerical values ​​recited. Instead, unless otherwise specified, each such dimension is intended to mean both the recited value and a functionally equivalent range around that value. For example, a dimension disclosed as "40 mm" is intended to mean "approximately 40 mm".

[0509] Unless expressly excluded or otherwise limited, each document cited herein, including any cross-referenced or related patent or patent application and any patent application or patent to which this application claims priority or the benefit of, is hereby incorporated by reference in its entirety. The citation of any document is not an admission that it is prior art to any of the present invention disclosed or claimed herein, or an admission that it, by itself or in combination with any one or more of the references, proposes, suggests, or discloses any such invention. In addition, to the extent that any meaning or definition of a term in this invention conflicts with any meaning or definition of the same term in a document incorporated by reference, the meaning or definition assigned to that term in this invention shall govern.

[0510] Although specific embodiments of the present invention have been illustrated and described, it will be apparent to those skilled in the art that various other changes and modifications may be made without departing from the spirit and scope of the present invention. Therefore, it is intended that all such changes and modifications within the scope of the present invention be covered in the appended claims.

Claims

1. A low-water content composition comprising: 1) at least one solid soluble composition domain (SDC) having a crystallizing agent; 2) at least one polyethylene glycol domain (PEGC); 3) an active agent; and wherein the crystallizing agent is a sodium salt of a saturated fatty acid having 8 to about 12 carbon atoms; wherein the active agent is present in at least one of the SDC or the PEGC.

2. The low water content composition according to claim 1, wherein the saturated fatty acid sodium salt of the crystallization agent comprises 50 wt% to 70 wt% of C12, 15 wt% to 25 wt% of C10, and 15 wt% to 25 wt% of C8.

3. The low water content composition of claim 1, wherein the saturated fatty acid sodium salt has a slow crystallization agent percentage (% Slow CA) between 50% and 70%.

4. The low water content composition according to any one of claims 1 to 3, wherein the crystallization agent in the SDC domain is in the form of fibers as determined by the "Fiber Test Method".

5. A low moisture content composition according to any one of the preceding claims, wherein the amount of water is less than 10% by weight of the final low moisture content composition as determined by the "Moisture Test Method".

6. A low moisture composition according to any one of the preceding claims, wherein the active agent is at least one of a fresh feel benefit agent, a fabric care active, a catalyst, an activator, a peroxide, an enzyme, an antimicrobial agent, a preservative, sodium chloride, a surfactant or a polyol, preferably wherein the fresh feel benefit agent is at least one of a fragrance or a deodorant.

7. A low water content composition according to any one of the preceding claims, wherein the active agent is at least one of the following: silicone oil, wax, essential oil, skin cooling agent, vitamin, sunscreen, bleaching particulate, antiperspirant active substance, cationic polymer or mixtures thereof, preferably wherein the active agent is at least one of the following: polyethylene wax, fish oil, jasmine, camphor, lavender, menthol, methyl lactate, vitamin A, vitamin E, perborate or mixtures thereof, more preferably wherein the fresh feeling benefit agent is at least one of the following: 3-(4-tert-butylphenyl)-2-methylpropanal, 3-(4-tert-butylphenyl)-propanal, 3-( 4-isopropylphenyl)-2-methylpropanal, 3-(3,4-methylenedioxyphenyl)-2-methylpropanal and 2,6-dimethyl-5-heptanal, α-damascone, β-damascone, γ-damascone, β-damascone, 6,7-dihydro-1,1,2,3,3-pentamethyl-4(5H)-indanone, methyl-7,3-dihydro-2H-1,5-benzodioxin-3-one, 2-[2-(4-methyl-3-cyclohexen-1-yl)propyl]cyclopentan-2-one, 2-sec-butylcyclohexanone, and β-dihydroionone, linalool, ethyl linalool, tetrahydrolinalool, dihydromyrcenol or mixtures thereof.

8. A low water content composition according to any one of the preceding claims, wherein the active agent is encapsulated in a capsule having a wall and a core, preferably wherein the capsule wall comprises at least one of: melamine, polyacrylamide, silicone, silicon dioxide, polystyrene, polyurea, polyurethane, polyacrylate-based materials, polyacrylate-based materials, gelatin, styrene malic anhydride, polyamide, aromatic alcohol, polyvinyl alcohol or mixtures thereof.

9. The low water content composition according to claim 8, wherein the active agent is a mixture of an active agent and an active agent capsule.

10. The low water content composition according to any one of the preceding claims, wherein the active agent is present in an amount of 1 wt% to 40 wt% based on the total weight of the low water content composition.

11. The low water content composition according to any one of the preceding claims, wherein the sodium salt is at least one of sodium C8, sodium C10 or sodium C12.

12. The low water content composition of any of the preceding claims, wherein the crystallization agent is present in an amount of about 70% to about 95% by weight of the low water content composition.

13. The low water content composition according to any one of the preceding claims, wherein the PEGC comprises PEG having a molecular weight of about 200 Daltons to about 50,000 Daltons.

14. A low moisture composition according to any one of the preceding claims, wherein there is humidity stability at 80% RH as determined by the Humidity Test Method.

15. A method for producing a low-water content composition, comprising: a) mixing-heating a crystallization agent and an aqueous phase until the crystallization agent is substantially dissolved, and cooling to a temperature before the crystallization agent significantly crystallizes in the form of SDCM; b) forming - forming the SDC into a designed shape and size by cooling the solid soluble composition mixture to below the crystallization temperature and allowing the solid soluble composition mixture to crystallize into an intermediate rheological solid; c) drying - removing excess water and producing a solid soluble composition (SDC) by removing between about 90% and about 99% of the water as determined by the "Water Test Method" from the intermediate rheology solid composition to produce a solid soluble composition having an average percent solubility greater than 5% at 37°C as determined by the "Dissolution Test Method"; d) providing polyethylene glycol (PEGC); e) mixing said SDC and said PEGC to produce a low water content composition having SDC domains and PEGC domains; wherein an active agent is added to at least one of the SDC domain or the PEGC domain.

Citation Information

Patent Citations

  • Dilute fabric care compositions comprising thickners and fabric care compositions for use in the presence of anionic carry-over

    US20060252668A1

  • Personal care compositions containing cationic synthetic copolymer and a detersive surfactant

    US20070207109A1

  • Delivery particle

    US20110268802A1

  • Cosmetic composition containing a cationic polymer and divalent metal salt for strengthening the hair

    US3958581A

  • Mild thickened shampoo compositions with conditioning properties

    US3962418A